Pre-oxidized fiber felt modification method for improving performance of electrode carbon felt and electrode carbon felt

The pre-oxidized fiber felt modification method using P(AN-co-IA) copolymer and UiO-66 powder, combined with δ-MnO2 surface treatment, addresses the limitations of existing carbon felt electrodes by enhancing conductivity and electrochemical activity, thus improving the performance of all-vanadium liquid flow batteries.

CN119133477AInactive Publication Date: 2024-12-13JIANGSU CANYUE CARBON FIBER COMPOSITE MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411291259.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing methods for modifying polyacrylonitrile carbon felt electrodes in all-vanadium liquid flow batteries are limited by the stability of the carbon structure, leading to inadequate electrocatalytic activity and hydrophobicity, which hinders the performance and scalability of these batteries.

Method used

A pre-oxidized fiber felt modification method using P(AN-co-IA) copolymer and UiO-66 powder, followed by carbonization and surface modification with δ-MnO2, enhances the conductivity and specific surface area of the electrode carbon felt, providing more reaction active sites and improving electrochemical properties.

Benefits of technology

The modified electrode carbon felt exhibits improved electrochemical activity, hydrophilicity, and mechanical strength, capable of handling large current charging and discharging requirements of all-vanadium liquid flow batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133477A_ABST
    Figure CN119133477A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flow batteries, and provides a pre-oxidized fiber felt modification method for improving the performance of an electrode carbon felt and the electrode carbon felt.The pre-oxidized fiber felt modification method comprises the steps that UiO-66 powder is added into a spinning solution, stirring and heating are conducted after mixing, a spinning solution is obtained, electrostatic spinning is conducted on the spinning solution, and a fiber felt is obtained; sequentially carrying out pre-oxidation, carbonization and surface activation treatment on the fiber felt to obtain an activated carbon felt; dispersing carbon dot powder in a dopamine solution to obtain a modified carbon dot dispersion liquid, soaking the activated carbon felt in the modified carbon dot dispersion liquid, taking out and drying, and performing high-temperature carbonization to obtain a modified carbon felt; uniformly mixing manganese sulfate, potassium permanganate and deionized water to obtain a reaction solution, transferring the reaction solution into a hydrothermal reaction kettle, soaking the modified carbon felt into the reaction solution for hydrothermal reaction, taking out the modified carbon felt after the reaction is finished, and washing and drying the modified carbon felt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid flow batteries and relates to a preoxidized fiber felt modification method for improving the performance of electrode carbon felt and the electrode carbon felt. Background Art

[0002] In recent years, renewable energy has attracted more and more attention due to its green and pollution-free advantages, and the shortcomings of the large-scale energy storage technology that matches it have attracted great attention. The all-vanadium liquid flow battery is a new type of green and environmentally friendly energy storage liquid flow battery system. The electrolyte is pressed into the battery stack through an external pump. Under the action of mechanical power, it circulates in the closed loop of different liquid storage tanks and half-cells. The proton exchange membrane is used as the separator of the battery pack. The electrolyte solution flows parallel to the electrode surface and undergoes electrochemical reactions. The current is collected and conducted through the double electrode plates, so that the chemical energy stored in the solution is converted into electrical energy. This reversible reaction process enables the vanadium battery to successfully complete charging, discharging and recharging.

[0003] All-vanadium liquid flow battery is a new type of green secondary battery. Its positive and negative electrolytes are all made of vanadium, which avoids cross contamination between the positive and negative electrodes. It has the advantages of flexible design, independent capacity, high safety and long life. It is used in power grid peak regulation systems and large-scale photovoltaic and wind power conversion systems. Although all-vanadium liquid flow batteries have begun to enter the commercial promotion stage, due to the influence of electrode materials and diaphragms, the development of all-vanadium liquid flow batteries has not yet reached the ideal large-scale application requirements.

[0004] One of the key factors affecting battery performance is the electrode material. Although it does not directly undergo electrochemical reactions, the performance of the electrode material is closely related to the electrocatalytic activity of the vanadium ion redox couple. Therefore, choosing a suitable electrode material can reduce the reaction activation energy, improve the reaction activity, and have significant surface structure effects and electrocatalytic characteristics. Since the electrolyte of the all-vanadium liquid flow battery is strongly acidic, the electrode material of the all-vanadium liquid flow battery is required to have good conductivity, strong acid resistance, excellent electrochemical activity, stable oxidation resistance and mechanical strength. At present, carbon felt is an electrode material that is widely studied and applied in all-vanadium liquid flow batteries due to its high specific surface area, high conductivity and low cost.

[0005] Currently, commercial all-vanadium flow batteries generally use polyacrylonitrile carbon felt electrodes, but because the inertness and hydrophobicity of carbon felt need to be improved, the modification of carbon felt has become one of the important means to improve the performance of electrode materials. At present, the main methods for modifying polyacrylonitrile carbon felt are air oxidation, liquid phase oxidation, electrochemical oxidation, etc. These modification methods mainly add oxygen-containing functional groups to the surface of carbon felt, which can help improve the electrochemical activity and hydrophilicity of the electrode carbon felt, and then catalyze the redox reaction of ion pairs, thereby improving the energy efficiency of all-vanadium flow batteries.

[0006] However, the commonality of the above modification measures is that the finished carbon felt is used as the raw material, and its fiber surface has been completely carbonized, so that the carbon structure and performance in the fiber are stable. The introduction of oxygen-containing functional groups based on stable carbon is bound to have limitations. With the increasing demand for all-vanadium liquid flow batteries, the demand for electrode carbon felt is also increasing year by year, and it is urgent to fundamentally solve the modification problem of electrode carbon felt. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a pre-oxidized fiber felt modification method and electrode carbon felt for improving the performance of electrode carbon felt. The present invention uses P(AN-co-IA) copolymer as the main polymer material of the spinning solution, and adds UiO-66 powder thereto, and then obtains activated carbon felt after electrostatic spinning, pre-oxidation, carbonization and surface activation treatment. During the carbonization process, UIO-66 powder is converted into amorphous carbon and ZrO2, thereby giving the activated carbon felt better conductivity and more reaction active sites; finally, using the activated carbon felt as a matrix, its surface is carbon-nitrogen dual-doped and in-situ modified with δ-MnO2, thereby significantly improving the specific surface area of ​​the electrode carbon felt and providing more abundant reaction active sites. The electrode carbon felt after surface modification has good electrochemical properties and can fully meet the large current charging and discharging requirements of all-vanadium liquid flow batteries.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, a preoxidized fiber felt modification method for improving the performance of electrode carbon felt, the preoxidized fiber felt modification method comprising:

[0010] (I) uniformly mixing acrylonitrile, itaconic acid and dimethyl sulfoxide to obtain a precursor solution, stirring and heating the precursor solution in a nitrogen atmosphere, then adding azobisisobutyronitrile to the precursor solution and continuously stirring and heating to initiate a polymerization reaction to generate a P(AN-co-IA) copolymer, obtaining a polymer solution after the reaction is completed, and adding dimethyl sulfoxide to the polymer solution for dilution to obtain a spinning solution;

[0011] (II) using zirconium ions as metal ions and 1,4-phthalic acid as organic ligands to prepare UiO-66 powder by solvothermal reaction, adding the UiO-66 powder to the spinning solution obtained in step (I), stirring and heating after mixing to obtain a spinning solution, electrospinning the spinning solution to obtain a fiber felt, and sequentially performing pre-oxidation, carbonization and surface activation treatment on the fiber felt to obtain an activated carbon felt;

[0012] (III) uniformly mixing citric acid, ethylenediamine and deionized water to obtain a carbon source solution, subjecting the carbon source solution to a hydrothermal reaction, and separating and purifying the reaction product after the reaction to obtain a carbon dot powder; dispersing the carbon dot powder in a dopamine solution to obtain a modified carbon dot dispersion, immersing the activated carbon felt obtained in step (II) in the modified carbon dot dispersion, taking out the activated carbon felt after a period of time, drying it, and obtaining a modified carbon felt after high-temperature carbonization;

[0013] (IV) Mix manganese sulfate, potassium permanganate and deionized water to obtain a reaction solution, transfer the reaction solution to a hydrothermal reactor, immerse the modified carbon felt obtained in step (III) in the reaction solution, and perform a hydrothermal reaction under stirring to generate δ-MnO2 in situ on the surface of the modified carbon felt. After the reaction is completed, take out the modified carbon felt, rinse it and dry it.

[0014] The present invention uses P(AN-co-IA) copolymer as the main material of the spinning solution, and mixes UiO-66 powder therein, and then obtains activated carbon felt after electrostatic spinning, pre-oxidation, carbonization and surface activation treatment. During the carbonization process, UiO-66 powder is converted into amorphous carbon and ZrO2, thereby giving the activated carbon felt better conductivity and more reaction active sites; finally, using the activated carbon felt as a matrix, its surface is carbon-nitrogen dual-doped and in-situ modified with δ-MnO2, which significantly increases the specific surface area of ​​the electrode carbon felt and provides more abundant reaction active sites. The electrode carbon felt after surface modification has good electrochemical properties and can fully meet the large current charging and discharging requirements of the all-vanadium liquid flow battery.

[0015] Polyacrylonitrile has high spinnability as a precursor of carbon felt fibers. However, since the cyano group in the polyacrylonitrile molecular chain cannot form strong intermolecular forces with the solvent dimethyl sulfoxide molecules, the polyacrylonitrile fibers formed in the spinning process are relatively dispersed, the fiber orientation is low, the gaps between fibers are large, and the density of the fiber felt obtained by spinning is poor. The cyclization degree of the polyacrylonitrile molecular chain after pre-oxidation is low, and the heat-resistant trapezoidal structure formed is small, which makes the polyacrylonitrile fiber unable to withstand the high-temperature carbonization process, so that the conductivity of the carbon felt obtained after carbonization cannot be significantly improved. In order to solve this problem, the present invention introduces itaconic acid into the acrylonitrile molecular chain to obtain a P(AN-co-IA) copolymer. Since the H in the carboxyl group on the itaconic acid monomer forms a hydrogen bond with the O in the S=O in the solvent dimethyl sulfoxide molecule, the solvent dimethyl sulfoxide is more tightly combined with the fiber during the spinning process to form a uniform and dense fiber bundle structure. In the subsequent pre-oxidation process, due to the introduction of the itaconic acid copolymer monomer containing two carboxylic acid functional groups, the pre-oxidation reaction of polyacrylonitrile is converted from a free radical cyclization reaction mechanism to an ion reaction mechanism, which greatly reduces the heat released in the pre-oxidation process, plays a role in promoting the cyclization reaction, and the disordered carbon structure obtained after carbonization is greatly increased, so that the cyclization degree and orientation degree of the fiber are higher and the fiber structure is denser.

[0016] The present invention uses a P(AN-co-IA) copolymer as a carbon precursor, and obtains an activated carbon felt after electrostatic spinning, pre-oxidation, carbonization and surface activation treatment. In order to improve the problem of poor electrochemical activity of the activated carbon felt, the present invention uses a solvent thermal method to synthesize a metal-organic framework UIO-66 powder, and introduces the UiO-66 powder into the P(AN-co-IA) copolymer spinning solution for spinning. The synthesized UIO-66 powder has a regular octahedral structure and a smooth surface. It is composed of three elements: Zr, O and C. Zr is used as a central atom and is connected to 1,4-phthalic acid through a covalent bond to form a MOF material with a large specific surface area and a porous structure. During the carbonization process, the octahedral structure of the UIO-66 powder shrinks and the surface becomes rough, but the complete octahedral skeleton is still retained. During the carbonization process, the zirconium ions are converted into metal oxide ZrO2 at high temperature, and the organic ligand 1,4-phthalic acid forms an amorphous carbon network structure after carbonization. The carbonized UIO-66 powder presents a carbon network-coated ZrO2 structure, which gives the activated carbon felt better conductivity and more reactive sites. This is because, on the one hand, the specific surface area of ​​the carbonized UIO-66 powder is lower than that before carbonization, and the pore size is increased. The carbonization process transforms the porous structure of the UIO-66 powder from micropores to mesopores. The increase in the number of mesopores is conducive to the transmission of electrolyte ions and to improving the cycle stability of the electrode carbon felt. On the other hand, the ZrO2 obtained after carbonization has a large specific surface area. The ZrO2 particles are evenly distributed in the fiber, providing more active sites for the electrode reaction. The defective carbon increases after high-temperature carbonization, and more defective carbon can also increase the number of reactive active sites. In addition, the carbonization process transforms the UIO-66 powder into a more stable ZrO2, avoiding the change of the structure of the carbonized UIO-66 powder during the battery charge and discharge process, making the electrode carbon felt have good cycle stability. At the same time, there are abundant oxygen-containing functional groups and unsaturated Zr on the surface of ZrO2. 4+ -O 2- Acid-base pairs have strong catalytic activity. Doping them into fibers can further enhance the catalytic activity of the electrode carbon felt, making the all-vanadium liquid flow battery have higher energy efficiency.

[0017] In the preparation process of carbon felt, the pre-oxidation process of fiber felt is a key step in preparing high-performance carbon felt. The present invention adopts a gradient heating method to pre-oxidize the fiber felt. The fiber undergoes a series of complex chemical reactions in the air, including cyclization, dehydrogenation and oxidation, and finally transforms into a heat-resistant ladder-shaped aromatic heterocycle. During the pre-oxidation process, the by-products inside the fiber diffuse from the inside to the outside, and oxygen diffuses from the outside to the inside to participate in the reaction. During the diffusion of oxygen into the fiber, it is first captured by the ring structure of the outer layer of the fiber. Therefore, the oxygen content of the outer layer of the fiber is higher than that of the inner layer. Due to the different oxygen content in the radial direction of the fiber, the pre-oxidation reaction degree of the fiber cortex is higher, while the pre-oxidation reaction degree of the fiber is lower. Therefore, the radial direction of the pre-oxidized fiber will form a skin-core structure with less internal structure and more complete external structure. The existence of this skin-core structure will affect the comprehensive mechanical properties of the carbonized fiber. In order to improve and prevent the appearance of the skin-core structure, the present invention applies a certain pressure to the fiber during the pre-oxidation process, thereby increasing the diffusion power of oxygen into the fiber, which helps to improve the uniformity of the radial structure of the fiber. In order to further improve the activation degree of carbon felt, the present invention uses sucrose solution as an active agent and modifies the surface of the carbon felt under a mild weak oxidizing activation atmosphere, which not only increases the number of active functional groups on the surface of the carbon felt, but also effectively controls the activation degree and uniformity of the fibers, and can also reduce the reaction degree between sucrose and the oxidizing atmosphere to a certain extent, thereby avoiding the reduction of the mechanical strength of the carbon felt due to excessive oxidation.

[0018] Since the activated carbon felt has a low hydrophilicity, when it is used as an electrode of an all-vanadium liquid flow battery, it will affect the surface wettability of the electrolyte to it, thereby causing the electrochemical performance of the all-vanadium liquid flow battery to decrease. To this end, the present invention performs a dip-coating modification treatment on the surface of the activated carbon felt, and carbon-nitrogen dual-doping the surface of the activated carbon felt with polydopamine and carbon dots, thereby enhancing the hydrophilicity of the electrode carbon felt and significantly improving the electrochemical activity of the electrode carbon felt. On this basis, δ-MnO2 is synthesized in situ to optimize the surface structure of the electrode carbon felt, giving the electrode carbon felt a rougher surface structure, which can make up for the defects of the doped electrode carbon felt, and provide a larger contact area and higher catalytic activity for the electrode reaction of the electrode carbon felt. Through carbon-nitrogen dual-doping and δ-MnO2 loading, the energy barrier of the electrochemical reaction is synergistically reduced, the transfer of electrons is accelerated, the activation overpotential is significantly reduced, and the electrochemical performance of the electrode carbon felt is greatly improved.

[0019] The present invention utilizes the self-polymerization characteristics of dopamine, and introduces nitrogen-containing functional groups on the surface of carbon felt using dopamine as a nitrogen source, thereby significantly improving the surface characteristics of the electrode carbon felt, enhancing the hydrophilicity of the electrode carbon felt, and improving the electrochemical activity of the electrode carbon felt. In addition, since polydopamine introduces a certain amount of nitrogen doping on the electrode carbon felt, it not only provides a large number of reactive sites for the electrochemical reaction, but also enhances the electrocatalytic activity of the electrode carbon felt, thereby improving the reversibility of the electrode reaction and significantly improving the kinetic performance of the electrode reaction of the all-vanadium liquid flow battery. The present invention compounds carbon dots in polydopamine, so that the electrode carbon felt after dip coating modification has a rougher surface structure, thereby significantly improving the specific surface area of ​​the electrode carbon felt, increasing the surface defects of the electrode carbon felt, and making the reactive sites on the surface of the electrode carbon felt more abundant, which is conducive to promoting the diffusion and transmission of ions, thereby improving the chemical kinetic process of the electrode carbon felt.

[0020] δ-MnO2 has a unique nano-layered structure, which gives it a high specific surface area and chemical properties. The present invention uses potassium permanganate and manganese sulfate as reaction raw materials to synthesize δ-MnO2 in situ on the surface of modified carbon felt, which can further improve the electrochemical properties of carbon felt and obtain electrode carbon felt with high specific capacity. Potassium permanganate is used as an oxidant to oxidize divalent manganese sulfate to form tetravalent manganese dioxide. At the same time, potassium ions in the solution will also make other forms of manganese dioxide produced during the generation process, which is conducive to the formation of δ-MnO2. The in-situ synthesized δ-MnO2 is uniformly attached to the fibers of the modified carbon felt, and its shape is a spherical cluster composed of nanosheets. These δ-MnO2 attached to the surface of the modified carbon felt fibers protect the modified carbon felt on the one hand and increase the contact area between the electrode carbon felt and the electrolyte; on the other hand, the lamellae flower cluster structure of δ-MnO2 has abundant interlayer gaps, which is convenient for the transmission of ions and the transfer of charges, and provides extremely abundant reactive active sites for electrolyte ions.

[0021] The present invention utilizes the synergistic effect of carbon dots and δ-MnO2 to significantly improve the electrochemical performance of the electrode carbon felt, wherein the carbon dots have good electrical conductivity, ideal specific surface area, good hydrophilicity, and abundant functional groups and active sites. After being compounded with δ-MnO2 having high capacity, the defects of low electrical conductivity and high ion diffusion resistance of δ-MnO2 are improved. In addition, the carbon dots loaded in the early stage also play a crucial role in the later synthesis of δ-MnO2. On the one hand, the carbon dots improve the electrical conductivity of δ-MnO2 and increase the ion reaction sites of the complex; on the other hand, the carbon dots also improve the sheet morphology of δ-MnO2, making the reaction process of trivalent manganese to tetravalent manganese faster, and the transmission efficiency of various ions is significantly improved. The overall synergistic effect of the two greatly improves the electrochemical performance of the electrode carbon felt after carbon dot / manganese dioxide composite modification.

[0022] As a preferred technical solution of the present invention, in step (I), the mass ratio of acrylonitrile, itaconic acid and dimethyl sulfoxide when mixed is (45-50):1:(210-220), for example, it can be 45:1:210, 45.5:1:211, 46:1:212, 46.5:1:213, 47:1:214, 47.5:1:215, 48:1:216, 48.5:1:217, 49:1:218, 49.5:1:219 or 50:1:220, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] In some optional instances, the stirring rate of the precursor solution is 350-450 r / min, for example, it can be 350 r / min, 360 r / min, 370 r / min, 380 r / min, 390 r / min, 400 r / min, 410 r / min, 420 r / min, 430 r / min, 440 r / min or 450 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In some optional examples, the stirring time of the precursor solution is 20 to 30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In some optional instances, the heating temperature of the precursor solution is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In some optional examples, the mass ratio of acrylonitrile to azobisisobutyronitrile in the precursor solution is (130-140):1, for example, it can be 130:1, 131:1, 132:1, 133:1, 134:1, 135:1, 136:1, 137:1, 138:1, 139:1 or 140:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional examples, the stirring rate of the polymerization reaction is 350-450 r / min, for example, it can be 350 r / min, 360 r / min, 370 r / min, 380 r / min, 390 r / min, 400 r / min, 410 r / min, 420 r / min, 430 r / min, 440 r / min or 450 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional examples, the stirring time of the polymerization reaction is 18 to 20 hours, for example, it can be 18 hours, 18.2 hours, 18.4 hours, 18.6 hours, 18.8 hours, 19 hours, 19.2 hours, 19.4 hours, 19.6 hours, 19.8 hours or 20 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional examples, the heating temperature of the polymerization reaction is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional examples, the mass fraction of the P(AN-co-IA) copolymer in the spinning solution obtained after dilution is 13 to 15 wt%, for example, it can be 13 wt%, 13.2 wt%, 13.4 wt%, 13.6 wt%, 13.8 wt%, 14 wt%, 14.2 wt%, 14.4 wt%, 14.6 wt%, 14.8 wt% or 15 wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] As a preferred technical solution of the present invention, in step (II), the UiO-66 powder is prepared by the following method:

[0032] Zirconium chloride, 1,4-phthalic acid and acetic acid are dissolved in N,N-dimethylformamide, mixed evenly and then ultrasonically dispersed to obtain a precursor solution; the precursor solution is transferred to a reactor, stirred and heated to react, and after the reaction is completed, the reaction product is washed and centrifuged in sequence, and the precipitate after centrifugation is dried to obtain the UiO-66 powder.

[0033] In some optional examples, the mixing ratio of the zirconium chloride, the 1,4-phthalic acid, the acetic acid and the N,N-dimethylformamide is 1mmol:1mmol:(3-5)mL:(25-35)mL, for example, it can be 1mmol:1mmol:3mL:25mL, 1mmol:1mmol:3.2mL:26mL, 1mmol:1mmol:3.4mL:27mL, 1mmol:1mmol:3.6mL:28mL, 1mmol:1mmol:3.8mL:29mL, 1mmol:1mmol:4mL:30mL, 1mmol:1mmol:4.2mL:31mL, 1mmol:1mmol:4.4mL:32mL, 1mmol:1mmol:4.6mL:33mL, 1mmol:1mmol:4.8mL:34mL or 1mmol:1mmol:5mL:35mL, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] In some optional examples, the ultrasonic power used in the ultrasonic dispersion is 200-300 W, for example, 200 W, 210 W, 220 W, 230 W, 240 W, 250 W, 260 W, 270 W, 280 W, 290 W or 300 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the ultrasonic dispersion time is 10 to 20 minutes, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional examples, the stirring rate of the precursor solution is 200-300 r / min, for example, it can be 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min or 300 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In some optional examples, the heating temperature of the precursor solution is 120-130°C, for example, it can be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In some optional examples, the reaction time of the precursor solution is 20 to 25 hours, for example, it can be 20 hours, 20.5 hours, 21 hours, 21.5 hours, 22 hours, 22.5 hours, 23 hours, 23.5 hours, 24 hours, 24.5 hours or 25 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In some optional examples, the centrifugal speed of the reaction product after washing is 8000-9000 r / min, for example, it can be 8000 r / min, 8100 r / min, 8200 r / min, 8300 r / min, 8400 r / min, 8500 r / min, 8600 r / min, 8700 r / min, 8800 r / min, 8900 r / min or 9000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional examples, the centrifugation time of the reaction product after washing is 3 to 5 min, for example, it can be 3.0 min, 3.2 min, 3.4 min, 3.6 min, 3.8 min, 4.0 min, 4.2 min, 4.4 min, 4.6 min, 4.8 min or 5.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional examples, the drying temperature of the precipitate is 80-100°C, for example, it can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional examples, the drying time of the precipitate is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] As a preferred technical solution of the present invention, in step (II), the mass fraction of UiO-66 powder in the spinning solution is 0.5-1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] The present invention specifically limits the mass fraction of UiO-66 powder in the spinning solution to 0.5-1.5wt%. When the addition amount of UiO-66 powder is less than 0.5wt%, the gaps between the fibers obtained by spinning are larger, the continuity between the UiO-66 powders is poor, and an effective and continuous electrolyte ion transmission channel cannot be formed, resulting in a higher energy required for ion transmission. When the addition amount of UiO-66 powder exceeds 1.5wt%, the UiO-66 powder has obvious agglomeration phenomenon on the surface and inside of the fiber. On the one hand, the UiO-66 powder agglomerates located inside the fiber will produce stress concentration phenomenon, thereby affecting the mechanical strength of the fiber; on the other hand, the "agglomerated nanocage" formed by the agglomeration of UiO-66 powder will also affect the transmission of electrolyte ions. When the addition amount of UiO-66 powder is within the range of 0.5-1.5wt%, the dispersion degree of UiO-66 powder is better, and there is both good continuity and no serious agglomeration phenomenon between UiO-66 powders.

[0045] In some optional examples, the heating temperature when the spinning solution and the UiO-66 powder are mixed is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional examples, the stirring rate when the spinning solution and the UiO-66 powder are mixed is 300-400 r / min, for example, it can be 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min, 350 r / min, 360 r / min, 370 r / min, 380 r / min, 390 r / min or 400 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some optional examples, the stirring time when the spinning solution and the UiO-66 powder are mixed is 10 to 15 hours, for example, it can be 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, 13.5 hours, 14 hours, 14.5 hours or 15 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In some optional examples, the needle diameter used in the electrospinning is 0.5 to 1.5 mm, for example, it can be 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm or 1.5 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] The present invention specifically limits the needle diameter used in electrospinning to 0.5-1.5 mm. The size of the needle diameter directly affects the diameter of the fiber obtained by spinning. When the needle diameter is lower than 0.5 mm, the diameter of the fiber obtained by spinning is too thin, which affects the mechanical strength of the fiber, thereby reducing the service life of the electrode carbon felt. When the needle diameter exceeds 1.5mm, the diameter of the fiber obtained by spinning is too thick. In the pre-oxidation stage, there is a large difference in the oxygen content of the cortex and the core of the fiber. The oxygen content of the cortex is higher, and the oxygen content decreases sharply from the cortex to the core. This is because the thicker diameter means that the diffusion distance of oxygen from the cortex to the core is longer, and the diffusion of oxygen is also accompanied by the oxidation reaction. Therefore, the oxidation reaction occurs first in the cortex. As the diffusion process proceeds, the degree of oxidation of the cortex deepens and the structure gradually becomes dense, making it difficult for oxygen to pass through the fiber cortex and enter the interior of the fiber. As a result, the oxidation reaction of the fiber core is incomplete and the oxygen content is low. In the subsequent carbonization stage, the lower oxygen content in the core causes a large number of small molecules to escape, thereby producing defects such as voids and holes in the fiber core, resulting in a decrease in the tensile strength of the fiber.

[0050] In some optional examples, the relative humidity of the electrospinning environment is 35-45%, for example, it can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional examples, the ambient temperature of the electrospinning is 30-40°C, for example, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In some optional examples, the voltage of the electrospinning is 20 to 30 kV, for example, 20 kV, 21 kV, 22 kV, 23 kV, 24 kV, 25 kV, 26 kV, 27 kV, 28 kV, 29 kV or 30 kV, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In some optional examples, the propulsion speed of the electrospinning is 1.5 to 2.5 mL / h, for example, it can be 1.5 mL / h, 1.6 mL / h, 1.7 mL / h, 1.8 mL / h, 1.9 mL / h, 2.0 mL / h, 2.1 mL / h, 2.2 mL / h, 2.3 mL / h, 2.4 mL / h or 2.5 mL / h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In some optional examples, the distance from the tip of the electrospinning needle to the receiving screen is 10 to 20 cm, for example, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, 16 cm, 17 cm, 18 cm, 19 cm or 20 cm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional examples, the thickness of the fiber felt is 1 to 3 mm, for example, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.2 mm, 2.4 mm, 2.6 mm, 2.8 mm or 3.0 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] As a preferred technical solution of the present invention, in step (II), the pre-oxidation process is carried out in an oxidation furnace, and the pre-oxidation process adopts a six-stage gradient pre-oxidation process, which specifically includes the following steps:

[0057] In an air atmosphere, the fiber felt is heated to a first pre-oxidation temperature at a first heating rate and kept warm to complete a first pre-oxidation process; then, it is heated to a second pre-oxidation temperature at a second heating rate and kept warm to complete a second pre-oxidation process; then, it is heated to a third pre-oxidation temperature at a third heating rate and kept warm to complete a third pre-oxidation process; then, it is heated to a fourth pre-oxidation temperature at a fourth heating rate and kept warm to complete a fourth pre-oxidation process; then, it is heated to a fifth pre-oxidation temperature at a fifth heating rate and kept warm to complete a fifth pre-oxidation process; then, it is heated to a sixth pre-oxidation temperature at a sixth heating rate and kept warm to complete a sixth pre-oxidation process; after the insulation is completed, it is cooled to room temperature to obtain a pre-oxidation felt.

[0058] In an air atmosphere, the fiber is continuously heated in a gradient according to a specific temperature spectrum, and a series of thermochemical reactions occur to form an insoluble and infusible pre-oxidized fiber with a heat-resistant trapezoidal structure. In the subsequent carbonization process, a unique chaotic layer graphite structure of carbon fiber can be formed, which gives the carbon felt excellent mechanical properties. However, the degree of oxidation reaction of the fiber cortex and core is different, resulting in the appearance of a skin-core structure. This uneven radial structure will be inherited by the subsequent carbonization treatment, thereby increasing the structural defects of the carbon fiber and limiting the improvement of the mechanical properties of the carbon fiber. In order to solve this problem, the present invention adopts a six-stage gradient heating process to replace the traditional four-stage gradient heating process.

[0059] The initial heating temperature of the traditional four-stage gradient heating process is too high and the heating rate is too fast, resulting in the pre-oxidation reaction not having enough time to proceed and the heat release being more concentrated. This concentrated heat release phenomenon causes a large number of defects inside the fiber. At the same time, due to the radial unevenness of the fiber pre-oxidation reaction, the oxidation reaction occurs rapidly in the fiber cortex and releases a large amount of heat, which affects the diffusion rate of oxygen into the fiber, making the cyclization reaction and oxidation reaction inside the fiber incomplete, resulting in the appearance of a skin-core structure, which ultimately affects the mechanical strength of the carbonized fiber.

[0060] The present invention adopts a six-stage gradient temperature rise pre-oxidation process to pre-oxidize the fiber felt. The six-stage gradient temperature rise pre-oxidation process is divided into an early stage, a middle stage and a late stage. Among them, the first pre-oxidation process and the second pre-oxidation process are the early stage, the third pre-oxidation process and the fourth pre-oxidation process are the middle stage, and the fifth pre-oxidation process and the sixth pre-oxidation process are the late stage.

[0061] For the cyclization reaction, in the four-stage gradient heating process, the cyclization reaction is more intense in the early stage of pre-oxidation, gradually weakens in the middle stage of pre-oxidation, and further slows down in the late stage of pre-oxidation; while in the six-stage gradient heating process, the cyclization reaction is dispersed in each stage, the cyclization reaction in the early stage of pre-oxidation is relatively weak, but the degree of cyclization in the middle and late stages of pre-oxidation is higher than that in the four-stage gradient heating process. This is because the six-stage gradient heating process increases the temperature gradient within the same pre-oxidation time, which is equivalent to reducing the heating rate, making the exothermic reaction peak wider, reducing the starting reaction temperature and the termination reaction temperature, and alleviating the phenomenon of heat concentration during the pre-oxidation process, thereby avoiding the concentrated occurrence of the cyclization reaction. Since the starting temperature of the six-stage gradient heating pre-oxidation is low, it will also allow sufficient buffer time for the early reaction of pre-oxidation, so that the fiber molecular chain will be deoriented at a lower temperature and undergo intramolecular cyclization reaction. The cyclization reaction is slower at a lower starting temperature, and the heat-resistant ladder structure formed by cyclization is more perfect. The starting temperature of the four-stage gradient heating pre-oxidation is relatively high, and the fiber molecules undergo a violent cyclization reaction at high temperature. The rapid and concentrated heat release will cause imperfections in the fiber structure. This defect will be transmitted to the carbonized fiber, ultimately affecting the mechanical properties of the carbon felt.

[0062] For the oxidation reaction, the starting temperature of the six-stage gradient heating pre-oxidation is low, the temperature difference between each stage is small, the oxidation reaction in the early stage of pre-oxidation is relatively slow, and the growth rate of oxygen content is low. In the middle and late stages of pre-oxidation, the degree of oxidation reaction gradually intensifies, and the growth rate of oxygen content increases significantly. However, the starting temperature of the four-stage gradient heating pre-oxidation is high, the temperature difference between each stage is large, and the degree of oxidation reaction in the early stage of pre-oxidation is relatively intense. During the entire pre-oxidation process, the growth rate of oxygen content continues to increase, and the reaction heat release is relatively concentrated. Rapid and large-scale concentrated heat release will cause imperfections in the fiber structure. This defect will be transmitted to the carbonized fiber, and ultimately affect the mechanical properties of the carbon felt.

[0063] The purpose of the present invention using a six-stage gradient temperature rise pre-oxidation process is to disperse the pre-oxidation temperature. By increasing the number of temperature gradients, the pre-oxidation reaction is divided into more stages, which reduces the starting temperature and the ending temperature, and is also equivalent to reducing the heating rate, which plays a role in alleviating the concentrated heat release of the reaction, so that the structural defects caused by concentrated heat release are greatly reduced. The pre-oxidation reaction starts from a lower starting temperature, which can slow down the early reaction rate, make the trapezoidal structure formed by the cyclization reaction more perfect, and reduce the generation of defects. The lower ending temperature and multi-stage temperature gradient are also conducive to slowing down the occurrence of the oxidation reaction, reducing the oxygen content, and making the distribution of the oxygen content in the radial direction of the fiber more uniform, avoiding the appearance of the skin-core structure.

[0064] In some optional instances, the first heating rate is 5 to 10°C / min, for example, it can be 5.0°C / min, 5.5°C / min, 6.0°C / min, 6.5°C / min, 7.0°C / min, 7.5°C / min, 8.0°C / min, 8.5°C / min, 9.0°C / min, 9.5°C / min or 10.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In some optional examples, the first pre-oxidation temperature is 220-225°C, for example, it can be 220°C, 220.5°C, 221°C, 221.5°C, 222°C, 222.5°C, 223°C, 223.5°C, 224°C, 224.5°C or 225°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] The cyclization reaction in the pre-oxidation process mainly occurs in the early stage of pre-oxidation when the temperature is relatively low, while the oxidation reaction occurs in the late stage of pre-oxidation when the temperature is relatively high. Therefore, the starting temperature of pre-oxidation will significantly affect the cyclization reaction rate in the early stage of pre-oxidation. The present invention specifically limits the first pre-oxidation temperature to 220-225°C. When the starting temperature is lower than 220°C, the cyclization reaction rate will decrease. Even if the subsequent reaction temperature is gradually increased, it cannot completely make up for the defects in the fiber structure caused by the insufficient degree of cyclization in the early stage. At the same time, this defect will also make the fiber structure after carbonization imperfect, which will ultimately affect the mechanical properties of the carbon felt.

[0067] When the starting temperature is higher than 225°C, the cyclization reaction will be too intense, resulting in excessively concentrated heat generation, which will cause more defects. In addition, too high a temperature will also cause the oxidation reaction, which is more sensitive to high temperatures, to proceed simultaneously, accelerating the oxidation reaction rate. Excessive oxygen content will be incorporated into the fiber molecular chain, causing a large number of small molecules to be removed during the subsequent carbonization process, thereby causing more defects inside the fiber, which will ultimately affect the mechanical properties of the carbon felt.

[0068] In some optional examples, the first pre-oxidation temperature is kept for 8 to 10 minutes, for example, 8.0 min, 8.2 min, 8.4 min, 8.6 min, 8.8 min, 9.0 min, 9.2 min, 9.4 min, 9.6 min, 9.8 min or 10.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] In some optional examples, during the first pre-oxidation process, the oxidation furnace is pressurized to 0.12-0.13 MPa while heating and raising the temperature, and the pressure is maintained while keeping the temperature. For example, it can be 0.12 MPa, 0.121 MPa, 0.122 MPa, 0.0123 MPa, 0.124 MPa, 0.125 MPa, 0.126 MPa, 0.127 MPa, 0.128 MPa, 0.129 MPa or 0.13 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] In some optional instances, the second heating rate is 2 to 5°C / min, for example, it may be 2.0°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min, 3.0°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4.0°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min or 5.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In some optional examples, the second pre-oxidation temperature is 230-235°C, for example, it can be 230°C, 230.5°C, 231°C, 231.5°C, 232°C, 232.5°C, 233°C, 233.5°C, 234°C, 234.5°C or 235°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] In some optional examples, the second pre-oxidation temperature is kept for 8 to 10 minutes, for example, 8.0 min, 8.2 min, 8.4 min, 8.6 min, 8.8 min, 9.0 min, 9.2 min, 9.4 min, 9.6 min, 9.8 min or 10.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] In some optional examples, during the second pre-oxidation process, the oxidation furnace is pressurized to 0.14-0.15 MPa while heating and raising the temperature, and the pressure is maintained while keeping the temperature. For example, it can be 0.14 MPa, 0.141 MPa, 0.142 MPa, 0.143 MPa, 0.144 MPa, 0.145 MPa, 0.146 MPa, 0.147 MPa, 0.148 MPa, 0.149 MPa or 0.15 MPa, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] Simply increasing the oxygen concentration in the pre-oxidation process will improve the radial structural differences of the fibers in different pre-oxidation stages to a certain extent. However, compared to simply increasing the oxygen concentration, applying a certain pressure during the pre-oxidation process will not only increase the oxygen concentration per unit volume, but also provide molecular kinetic energy, thereby increasing the diffusion power of the oxygen content into the fiber. There are both concentration differences and pressure differences in the radial direction of the fiber, thereby increasing the overall pre-oxidation reaction degree of the fiber, and improving the radial structural differences of the fiber more significantly. Therefore, the present invention applies different pre-oxidation pressures in different pre-oxidation stages to achieve the purpose of eliminating the radial differences of the pre-oxidized fibers.

[0075] The present invention applies a certain pressure to the fiber in the first pre-oxidation process and the second pre-oxidation process. Under the action of pressure, the oxygen element first undergoes an oxidation reaction with the cyclized structure, thereby reducing the content of C=N functional groups in the fiber. Therefore, by applying a certain pressure gradient in the initial stage of pre-oxidation, the cyclization reaction of the initial pre-oxidized structure fiber will be inhibited, but the oxidation reaction will be promoted.

[0076] In the first pre-oxidation stage, the present invention applies a pre-oxidation pressure of 0.12 to 0.13 MPa to the fiber, which increases the kinetic energy of gas molecules, increases the energy of gas molecules, promotes the diffusion of oxygen content in the radial direction of the fiber, and is conducive to accelerating the oxidation reaction rate of the fiber core, so that the oxidation degree of the fiber core is greatly improved, and the fiber core area is gradually reduced, while the change in the oxidation degree of the cortex is not obvious, and the radial structural difference of the fiber is gradually reduced. In the second pre-oxidation stage, the present invention applies a pre-oxidation pressure of 0.14 to 0.15 MPa to the fiber, the increasing trend of the pre-oxidation reaction degree of the fiber is gradually slowed down, the promoting effect of pressure on the oxidation reaction degree is weakened, and the radial structural difference of the fiber is further reduced.

[0077] The present invention is pressurized in two steps at the initial stage of pre-oxidation, first pressurized to 0.12-0.13MPa, and then continued to pressurize to 0.14-0.15MPa. This is because in the initial stage of pre-oxidation, oxygen needs to diffuse from the cortex to the core, and oxygen atoms will also be captured by the cyclic structure of the fiber cortex. These two processes are mutually competitive. When a smaller pressure is applied in the first pre-oxidation stage, the capture effect of the cyclic structure on oxygen atoms dominates. If too much pressure is applied in the first pre-oxidation stage, it will only further increase the degree of oxidation reaction of the cortex, and the contribution to the oxidation reaction of the core is very limited. After the first pre-oxidation stage is over, the oxygen atoms break through the capture of the cortex and begin to diffuse inward. At this time, the second pre-oxidation stage is entered. The pressure is increased to allow the oxygen diffusion effect to dominate, and oxygen is promoted to quickly enter the fiber core, so as to effectively increase the degree of oxidation reaction of the core. As the pressure further increases, the diffusion degree of oxygen tends to saturation, and the influence on the overall degree of oxidation reaction of the fiber also tends to be gentle. Even if the pressure is increased again, it is difficult to quickly increase the degree of oxidation reaction of the fiber, and the pre-oxidation mid-stage is entered at this time.

[0078] In some optional instances, the third heating rate is 2 to 5°C / min, for example, it may be 2.0°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min, 3.0°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4.0°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min or 5.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] In some optional examples, the third pre-oxidation temperature is 240-245°C, for example, it can be 240°C, 240.5°C, 241°C, 241.5°C, 242°C, 242.5°C, 243°C, 243.5°C, 244°C, 244.5°C or 245°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0080] In some optional examples, the third pre-oxidation temperature is kept for 8 to 10 minutes, for example, 8.0 min, 8.2 min, 8.4 min, 8.6 min, 8.8 min, 9.0 min, 9.2 min, 9.4 min, 9.6 min, 9.8 min or 10.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0081] In some optional examples, during the third pre-oxidation process, the pressure in the oxidation furnace is reduced to 0.12-0.13 MPa while heating and raising the temperature, and the pressure is maintained while keeping the temperature. For example, it can be 0.12 MPa, 0.121 MPa, 0.122 MPa, 0.123 MPa, 0.124 MPa, 0.125 MPa, 0.126 MPa, 0.127 MPa, 0.128 MPa, 0.129 MPa or 0.13 MPa, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] In some optional instances, the fourth heating rate is 2 to 5°C / min, for example, it may be 2.0°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min, 3.0°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4.0°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min or 5.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0083] In some optional examples, the fourth pre-oxidation temperature is 245-250°C, for example, it can be 245°C, 245.5°C, 246°C, 246.5°C, 247°C, 247.5°C, 248°C, 248.5°C, 249°C, 249.5°C or 250°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] In some optional examples, the fourth pre-oxidation temperature is kept for 8 to 10 minutes, for example, 8.0 min, 8.2 min, 8.4 min, 8.6 min, 8.8 min, 9.0 min, 9.2 min, 9.4 min, 9.6 min, 9.8 min or 10.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0085] In some optional examples, during the fourth pre-oxidation process, the pressure in the oxidation furnace is continuously reduced to 0.1-0.11 MPa while the temperature is increased, and the pressure is maintained while the temperature is maintained. For example, the pressure may be 0.1 MPa, 0.101 MPa, 0.102 MPa, 0.103 MPa, 0.104 MPa, 0.105 MPa, 0.106 MPa, 0.107 MPa, 0.108 MPa, 0.109 MPa or 0.11 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0086] The present invention gradually decompresses the fiber in the middle stage of pre-oxidation. This is because, as the pressure increases, the pre-oxidation reaction degree of the fiber cortex and core will be promoted, but the promotion effect on the pre-oxidation reaction degree of the fiber cortex is more obvious, which causes the radial structural difference of the pre-oxidized fiber to increase again. This is because the fiber has produced a certain radial difference and skin-core structure in the middle stage of pre-oxidation. Applying pressure in the middle stage of pre-oxidation cannot break through the reaction barrier of the fiber cortex and core. Therefore, when the oxygen element enters the fiber core, it will first react with the fiber cortex, so that the oxygen element entering the fiber core is reduced, and the pre-oxidation reaction degree of the core is lower than that of the cortex, resulting in a more obvious increase in the pre-oxidation reaction degree of the cortex, and the radial structural difference of the pre-oxidized fiber is greater.

[0087] However, for the preoxidized fibers formed in the initial stage of preoxidation, the radial structural differences of the preoxidized fibers will gradually decrease with the increase of pressure. This is because, on the one hand, there is no radial structural difference in the preoxidized fibers formed in the initial stage. Therefore, applying pressure in the initial stage of preoxidation will promote the overall preoxidation reaction degree of the fibers; on the other hand, in the initial stage of preoxidation, the preoxidized fibers have not yet formed a skin-core structure. At this time, under the action of pressure, oxygen atoms can break through the reaction barrier between the cortex and core of the fiber and enter the interior of the fiber, making the preoxidation reaction degrees of the fiber cortex and core basically the same, and the radial structural differences of the fibers are small.

[0088] In some optional instances, the fifth heating rate is 2 to 5°C / min, for example, it may be 2.0°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min, 3.0°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4.0°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min or 5.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0089] In some optional instances, the fifth pre-oxidation temperature is 250-255°C, for example, it can be 250°C, 250.5°C, 251°C, 251.5°C, 252°C, 252.5°C, 253°C, 253.5°C, 254°C, 254.5°C or 255°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] In some optional examples, the fifth pre-oxidation temperature is kept for 8 to 10 minutes, for example, 8.0 min, 8.2 min, 8.4 min, 8.6 min, 8.8 min, 9.0 min, 9.2 min, 9.4 min, 9.6 min, 9.8 min or 10.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0091] In some optional examples, during the fifth pre-oxidation process, the oxidation furnace is pressurized to 0.12-0.13 MPa while heating and raising the temperature, and the pressure is maintained while keeping the temperature. For example, it can be 0.12 MPa, 0.121 MPa, 0.122 MPa, 0.0123 MPa, 0.124 MPa, 0.125 MPa, 0.126 MPa, 0.127 MPa, 0.128 MPa, 0.129 MPa or 0.13 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0092] In some optional instances, the sixth heating rate is 2 to 5°C / min, for example, it may be 2.0°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min, 3.0°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4.0°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min or 5.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0093] In some optional examples, the sixth pre-oxidation temperature is 255-260°C, for example, it can be 255°C, 255.5°C, 256°C, 256.5°C, 257°C, 257.5°C, 258°C, 258.5°C, 259°C, 259.5°C or 260°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0094] The present invention specifically limits the sixth pre-oxidation temperature to 255-260°C. The termination temperature of pre-oxidation will significantly affect the mechanical properties of the pre-oxidized fiber. A termination temperature lower than 255°C or higher than 260°C will reduce the mechanical properties of the pre-oxidized fiber. This is because, in the later stage of pre-oxidation, the cyclization reaction gradually slows down and the oxidation reaction is more intense. The change in the termination temperature has a greater impact on the oxidation reaction that is sensitive to high temperature. As the termination temperature increases, the cyclization reaction changes less, while the oxygen content increases significantly. When the termination temperature is higher than 260°C, the oxygen content in the fiber will be too high, and a large number of small molecules will be removed during the subsequent carbonization process, resulting in more defects such as holes and voids, which ultimately affect the mechanical properties of the pre-oxidized fiber. When the termination temperature is lower than 255°C, the oxidation reaction of the core of the fiber will be incomplete, and the fiber structure will be imperfect, resulting in defects in the internal structure of the fiber during the carbonization process.

[0095] In some optional examples, the sixth pre-oxidation temperature is kept for 8 to 10 minutes, for example, 8.0 min, 8.2 min, 8.4 min, 8.6 min, 8.8 min, 9.0 min, 9.2 min, 9.4 min, 9.6 min, 9.8 min or 10.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0096] In some optional examples, during the sixth pre-oxidation process, the oxidation furnace is pressurized to 0.13-0.14 MPa while heating and raising the temperature, and the pressure is maintained while keeping the temperature. For example, it can be 0.13 MPa, 0.131 MPa, 0.132 MPa, 0.133 MPa, 0.134 MPa, 0.135 MPa, 0.136 MPa, 0.137 MPa, 0.138 MPa, 0.139 MPa or 0.14 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0097] Since the pre-oxidized fiber in the middle stage of pre-oxidation begins to have a skin-core structure and radial structure differences, the purpose of applying pressure in the late stage of pre-oxidation is mainly to increase the pre-oxidation degree of the core of the mid-term pre-oxidized fiber and alleviate the radial structure differences of the fiber. Gradually increasing the pressure in the late stage of pre-oxidation will promote the diffusion of oxygen elements into the fiber core, which is conducive to deepening the pre-oxidation reaction degree of the fiber cortex and core, but the deepening effect of the oxidation reaction degree of the fiber cortex and core is different. In the fifth pre-oxidation process, the pre-oxidation reaction degree of the fiber core increases nearly linearly with the increase of pressure, and although the pre-oxidation reaction degree of the cortex increases, the increasing trend gradually slows down, so that the radial structure difference of the fiber gradually decreases. In the sixth pre-oxidation process, the pre-oxidation reaction degree of the fiber core increases further, while the pre-oxidation reaction degree of the cortex tends to be gentle, and the radial structure difference of the fiber is further reduced.

[0098] As a preferred technical solution of the present invention, in step (II), the carbonization process specifically comprises the following steps:

[0099] In a nitrogen atmosphere, the pre-oxidized felt obtained after pre-oxidation is heated to a first carbonization temperature at a seventh heating rate and kept warm to complete a low-temperature carbonization process; then, it is continued to be heated to a second carbonization temperature at an eighth heating rate and kept warm to complete a high-temperature carbonization process; after the insulation is completed, it is cooled to room temperature to obtain a carbon felt.

[0100] In some optional instances, the seventh heating rate is 5 to 8°C / min, for example, it may be 5.0°C / min, 5.2°C / min, 5.4°C / min, 5.6°C / min, 5.8°C / min, 6.0°C / min, 6.2°C / min, 6.4°C / min, 6.6°C / min, 6.8°C / min, 7.0°C / min, 7.2°C / min, 7.4°C / min, 7.6°C / min, 7.8°C / min or 8.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0101] In some optional examples, the first carbonization temperature is 600-700°C, for example, it can be 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0102] In some optional examples, the first carbonization temperature is kept warm for 3 to 6 minutes, for example, 3.0 min, 3.2 min, 3.4 min, 3.6 min, 3.8 min, 4.0 min, 4.2 min, 4.4 min, 4.6 min, 4.8 min, 5.0 min, 5.2 min, 5.4 min, 5.6 min, 5.8 min or 6.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0103] In some optional instances, the eighth heating rate is 5 to 8°C / min, for example, it may be 5.0°C / min, 5.2°C / min, 5.4°C / min, 5.6°C / min, 5.8°C / min, 6.0°C / min, 6.2°C / min, 6.4°C / min, 6.6°C / min, 6.8°C / min, 7.0°C / min, 7.2°C / min, 7.4°C / min, 7.6°C / min, 7.8°C / min or 8.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0104] In some optional examples, the second carbonization temperature is 1500-1600°C, for example, it can be 1500°C, 1510°C, 1520°C, 1530°C, 1540°C, 1550°C, 1560°C, 1570°C, 1580°C, 1590°C or 1600°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0105] In some optional examples, the second carbonization temperature is kept warm for 2 to 4 minutes, for example, 2.0 min, 2.2 min, 2.4 min, 2.6 min, 2.8 min, 3.0 min, 3.2 min, 3.4 min, 3.6 min, 3.8 min or 4.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0106] As a preferred technical solution of the present invention, in step (II), the surface activation treatment process includes:

[0107] The sucrose solution is uniformly sprayed on the surface of the carbon felt. After drying, the carbon felt sprayed with the sucrose solution is placed in an activation furnace, and an activation gas is introduced into the activation furnace to heat and activate the carbon felt. After the heating activation is completed, the carbon felt is cooled to room temperature to complete the surface activation treatment and obtain the activated carbon felt.

[0108] In some optional examples, the mass fraction of the sucrose solution is 1 to 2 wt%, for example, it can be 1.0 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt% or 2.0 wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0109] In some optional examples, the spraying amount of the sucrose solution on the surface of the carbon felt is 4-5 mL / m 2 , for example, it can be 4.0 mL / m 2 , 4.1mL / m2 , 4.2mL / m 2 , 4.3mL / m 2 4.4mL / m 2 , 4.5mL / m 2 , 4.6mL / m 2 , 4.7mL / m 2 , 4.8mL / m 2 , 4.9mL / m 2 or 5.0 mL / m 2 , but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0110] In some optional instances, the activation gas is composed of argon, air and carbon dioxide, wherein the volume flow ratio of the argon, air and carbon dioxide is 1:(0.5-0.6):(0.2-0.3), for example, it can be 1:0.5:0.2, 1:0.51:0.21, 1:0.52:0.22, 1:0.53:0.23, 1:0.54:0.24, 1:0.55:0.25, 1:0.56:0.26, 1:0.57:0.27, 1:0.58:0.28, 1:0.59:0.29 or 1:0.6:0.3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0111] In some optional embodiments, the flow rate of the activated gas is 80 to 120 m 3 / h, for example, 80m 3 / h、85m 3 / h、90m 3 / h、95m 3 / h、100m 3 / h、105m 3 / h、110m 3 / h、115m 3 / h or 120m 3 / h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0112] In some optional examples, the heating rate of the heating activation is 10 to 12°C / min, for example, it can be 10.0°C / min, 10.2°C / min, 10.4°C / min, 10.6°C / min, 10.8°C / min, 11.0°C / min, 11.2°C / min, 11.4°C / min, 11.6°C / min, 11.8°C / min or 12.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0113] In some optional examples, the heating temperature for the heat activation is 900-1000°C, for example, it can be 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C or 1000°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0114] In some optional examples, the holding time for the heating activation is 15 to 25 minutes, for example, it can be 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes or 25 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0115] As a preferred technical solution of the present invention, in step (III), the molar ratio of citric acid to ethylenediamine is 1:(18-20), for example, it can be 1:18, 1:18.2, 1:18.4, 1:18.6, 1:18.8, 1:19, 1:19.2, 1:19.4, 1:19.6, 1:19.8 or 1:20, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0116] In some optional examples, the mixing ratio of citric acid and deionized water is 1g:(100-120)mL, for example, it can be 1g:100mL, 1g:102mL, 1g:104mL, 1g:106mL, 1g:108mL, 1g:110mL, 1g:112mL, 1g:114mL, 1g:116mL, 1g:118mL or 1g:120mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0117] In some optional examples, before the carbon source solution is subjected to a hydrothermal reaction, an alkali solution with a mass fraction of 20 to 30 wt% is added dropwise to the carbon source solution to adjust its pH value to 8 to 9, wherein the mass fraction of the alkali solution can be 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt% or 30 wt%, and the pH value can be adjusted to 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0118] In some optional examples, the temperature of the hydrothermal reaction of the carbon source solution is 170-180°C, for example, it can be 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0119] In some optional examples, the hydrothermal reaction time of the carbon source solution is 10 to 15 hours, for example, it can be 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, 13.5 hours, 14 hours, 14.5 hours or 15 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0120] In some optional examples, the separation and purification process includes: centrifugal filtration of the reaction product, dialysis of the supernatant after centrifugal filtration, and freeze-drying of the dialysis retentate.

[0121] In some optional examples, during the separation and purification process, the centrifugal speed of the centrifugal filtration is 8000-9000 r / min, for example, it can be 8000 r / min, 8100 r / min, 8200 r / min, 8300 r / min, 8400 r / min, 8500 r / min, 8600 r / min, 8700 r / min, 8800 r / min, 8900 r / min or 9000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0122] In some optional examples, during the separation and purification process, the centrifugation time of the centrifugal filtration is 10 to 20 minutes, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0123] In some optional examples, during the separation and purification process, the molecular weight cutoff of the dialysis bag used for dialysis is 800-1000Da, for example, it can be 800Da, 820Da, 840Da, 860Da, 880Da, 900Da, 920Da, 940Da, 960Da, 980Da or 1000Da, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0124] In some optional examples, during the separation and purification process, the freeze-drying temperature is -50 to -60°C, for example, it can be -50°C, -51°C, -52°C, -53°C, -54°C, -55°C, -56°C, -57°C, -58°C, -59°C or -60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0125] In some optional examples, during the separation and purification process, the freeze-drying time is 20 to 25 hours, for example, it can be 20 hours, 20.5 hours, 21 hours, 21.5 hours, 22 hours, 22.5 hours, 23 hours, 23.5 hours, 24 hours, 24.5 hours or 25 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0126] In some optional examples, the dopamine solution consists of dopamine hydrochloride and Tris-HCl buffer.

[0127] In some optional examples, the concentration of dopamine hydrochloride in the dopamine solution is 0.5-1.5 g / L, for example, it can be 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1.0 g / L, 1.1 g / L, 1.2 g / L, 1.3 g / L, 1.4 g / L or 1.5 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0128] In some optional examples, the mass ratio of the carbon dot powder to the dopamine hydrochloride in the dopamine solution is 1:(1.3-1.5), for example, it can be 1:1.3, 1:1.32, 1:1.34, 1:1.36, 1:1.38, 1:1.4, 1:1.42, 1:1.44, 1:1.46, 1:1.48 or 1:1.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0129] In the present invention, the introduction of carbon dots reduces the high resistance of δ-MnO2 itself, and at the same time enhances the hydrophilicity of the electrode carbon felt, so that the contact impedance and electron transfer impedance of the electrode carbon felt are reduced to a certain extent, and the transfer of electrons and the transmission of ions are promoted. At the same time, the combination of carbon dots and δ-MnO2 improves the load stability of δ-MnO2 and carbon felt, and enhances the cycle performance of the electrode carbon felt.

[0130] The present invention specifically limits the mass ratio of carbon dot powder to dopamine hydrochloride in the dopamine solution to 1:(1.3-1.5). When the amount of carbon dot powder added is lower than the lower limit of the range defined by the present invention, the improvement of the hydrophilicity of the electrode carbon felt is limited, thereby affecting the wettability of the electrolyte to the electrode carbon felt; at the same time, the addition of carbon dots will reduce the high resistance of δ-MnO2 itself. When the amount of carbon dots added is insufficient, the high resistance of δ-MnO2 cannot be effectively suppressed, thereby resulting in a decrease in the electron transmission capacity of the electrode carbon felt and the inability to fully exert the electrochemical properties of the electrode carbon felt; when the amount of carbon dot powder added exceeds the upper limit of the range defined by the present invention, excess carbon dots will cover the clustered lamellar structure of δ-MnO2, block the pores and gaps of δ-MnO2, resulting in difficulty for electrolyte ions to diffuse into the gaps of δ-MnO2, resulting in excessive ineffective dead volume of δ-MnO2, which hinders the diffusion process of electrolyte ions and ultimately leads to a decrease in the electrochemical properties of the electrode carbon felt.

[0131] In some optional examples, the ratio of the activated carbon felt to the modified carbon dot dispersion is 1g:(100-120)mL, for example, it can be 1g:100mL, 1g:102mL, 1g:104mL, 1g:106mL, 1g:108mL, 1g:110mL, 1g:112mL, 1g:114mL, 1g:116mL, 1g:118mL or 1g:120mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0132] In some optional examples, the immersion time of the activated carbon felt in the modified carbon dot dispersion is 5 to 10 hours, for example, it can be 5.0 hours, 5.5 hours, 6.0 hours, 6.5 hours, 7.0 hours, 7.5 hours, 8.0 hours, 8.5 hours, 9.0 hours, 9.5 hours or 10.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0133] In some optional examples, the drying temperature of the activated carbon felt is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0134] In some optional examples, the drying time of the activated carbon felt is 3 to 5 hours, for example, it can be 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4.0h, 4.2h, 4.4h, 4.6h, 4.8h or 5.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0135] In some optional examples, the high-temperature carbonization temperature of the activated carbon felt is 850-950°C, for example, it can be 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0136] In some optional examples, the high-temperature carbonization time of the activated carbon felt is 0.5 to 1.5 h, for example, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h or 1.5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0137] As a preferred technical solution of the present invention, in step (IV), the concentration of manganese sulfate in the reaction solution is 15-25 g / L, for example, it can be 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, 20 g / L, 21 g / L, 22 g / L, 23 g / L, 24 g / L or 25 g / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0138] In some optional examples, the concentration of potassium permanganate in the reaction solution is 110-120 g / L, for example, it can be 110 g / L, 111 g / L, 112 g / L, 113 g / L, 114 g / L, 115 g / L, 116 g / L, 117 g / L, 118 g / L, 119 g / L or 120 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0139] In some optional examples, the ratio of the modified carbon felt to the reaction solution is 1g:(100-120)mL, for example, it can be 1g:100mL, 1g:102mL, 1g:104mL, 1g:106mL, 1g:108mL, 1g:110mL, 1g:112mL, 1g:114mL, 1g:116mL, 1g:118mL or 1g:120mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0140] In some optional examples, the temperature of the hydrothermal reaction is 130-150°C, for example, it can be 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, 142°C, 144°C, 146°C, 148°C or 150°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0141] In some optional examples, the hydrothermal reaction time is 15 to 20 hours, for example, 15 hours, 15.5 hours, 16 hours, 16.5 hours, 17 hours, 17.5 hours, 18 hours, 18.5 hours, 19 hours, 19.5 hours or 20 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0142] In some optional examples, the stirring rate of the hydrothermal reaction is 400-500 r / min, for example, it can be 400 r / min, 410 r / min, 420 r / min, 430 r / min, 440 r / min, 450 r / min, 460 r / min, 470 r / min, 480 r / min, 490 r / min or 500 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0143] In some optional examples, the drying temperature is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0144] In some optional examples, the drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0145] In a second aspect, the present invention provides an electrode carbon felt prepared by the pre-oxidized fiber felt modification method for improving the performance of the electrode carbon felt described in the first aspect.

[0146] Compared with the prior art, the present invention has the following beneficial effects:

[0147] The present invention uses P(AN-co-IA) copolymer as the main material of the spinning solution, and mixes UiO-66 powder therein, and then obtains activated carbon felt after electrostatic spinning, pre-oxidation, carbonization and surface activation treatment. During the carbonization process, UiO-66 powder is converted into amorphous carbon and ZrO2, thereby giving the activated carbon felt better conductivity and more reaction active sites; finally, using the activated carbon felt as a matrix, its surface is carbon-nitrogen dual-doped and in-situ modified with δ-MnO2, which significantly increases the specific surface area of ​​the electrode carbon felt and provides more abundant reaction active sites. The electrode carbon felt after surface modification has good electrochemical properties and can fully meet the large current charging and discharging requirements of the all-vanadium liquid flow battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0148] Figure 1 A process flow chart of pre-oxidized fiber felt modification provided in Examples 1-5 of the present invention;

[0149] Figure 2 This is a scanning electron microscope image of the uncarbonized UIO-66 powder prepared in Example 1 of the present invention;

[0150] Figure 3 This is a scanning electron microscope image of the carbonized UIO-66 powder in the activated carbon felt prepared in Example 1 of the present invention;

[0151] Figure 4 This is a scanning electron microscope image of the fiber surface of the fiber mat prepared in Example 1 of the present invention;

[0152] Figure 5 This is an infrared spectrum of the UIO-66 powder prepared in Example 1 of the present invention before and after carbonization;

[0153] Figure 6 This is a scanning electron microscope image of the fiber surface of the electrode carbon felt prepared in Example 1 of the present invention at a low magnification;

[0154] Figure 7 This is a scanning electron microscope image of the fiber surface of the electrode carbon felt prepared in Example 1 of the present invention at a high magnification;

[0155] Figure 8 This is a transmission electron microscope image of the fiber surface of the electrode carbon felt prepared in Example 1 of the present invention;

[0156] Fig. 9 The cyclic voltammetry curves of the positive electrodes of the electrode carbon felts prepared in Example 1 of the present invention and Comparative Example 9;

[0157] Fig.10 The cyclic voltammetry curves of the negative electrode of the electrode carbon felt prepared in Example 1 of the present invention and Comparative Example 9;

[0158] Fig.11 The electrochemical impedance spectra of the positive electrodes of the electrode carbon felts prepared in Example 1 and Comparative Example 9 of the present invention;

[0159] Fig.12 The electrochemical impedance spectra of the negative electrode of the electrode carbon felt prepared in Example 1 of the present invention and Comparative Example 9 are shown;

[0160] Fig.13 The energy efficiency variation curves of the all-vanadium liquid flow battery assembled with the electrode carbon felt provided by Example 1 of the present invention and Comparative Example 9 at different current densities are shown. DETAILED DESCRIPTION

[0161] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0162] The chemical reagents used in the specific implementation are all commercially available products, and their models, specifications and manufacturer information are as follows:

[0163] Acrylonitrile: purity ≥99.5%, purchased from Jinan Century Tongda Chemical Co., Ltd.;

[0164] Itaconic acid: S30469-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0165] Dimethyl sulfoxide: S24295-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0166] Azobisisobutyronitrile: HFD-033, purchased from Jinan Huifengda Chemical Co., Ltd.;

[0167] Zirconium chloride: D69001, purchased from Shanghai Myril Biochemical Technology Co., Ltd.;

[0168] 1,4-Benzenedicarboxylic acid: S30133-100 g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0169] Acetic acid: industrial grade, purchased from Shandong Tongfengqi Chemical Co., Ltd.;

[0170] N,N-dimethylformamide: purity ≥99.9%, purchased from Shandong Jinyueyuan New Materials Co., Ltd.;

[0171] Sucrose: S11055-500 g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0172] Citric acid: B23391-20 mg, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0173] Ethylenediamine: purity ≥99%, purchased from Nanjing Chemical Reagent Co., Ltd.;

[0174] Sodium hydroxide: purity ≥99.5%, purchased from Nanjing Chemical Reagent Co., Ltd.;

[0175] Dopamine hydrochloride: purity ≥99%, purchased from Hubei Yongkuo Technology Co., Ltd.;

[0176] Tris-HCl buffer: PM12104, purchased from Shanghai Chuangsai Technology Co., Ltd.;

[0177] Manganese sulfate: purity ≥99.9%, purchased from Jinan Xinyue Chemical Co., Ltd.

[0178] Potassium permanganate: purity ≥99.9%, purchased from Nanjing Chemical Reagent Co., Ltd.

[0179] Example 1

[0180] This embodiment provides a method for modifying preoxidized fiber felt to improve the performance of electrode carbon felt, such as Figure 1 As shown, the preoxidized fiber felt modification method specifically comprises the following steps:

[0181] (1) acrylonitrile, itaconic acid and dimethyl sulfoxide were mixed uniformly in a mass ratio of 45:1:210 to obtain a precursor solution, and the precursor solution was stirred and heated in a nitrogen atmosphere, wherein the stirring rate was 350 r / min, the stirring time was 30 min, and the heating temperature was 60° C.;

[0182] Subsequently, azobisisobutyronitrile is added to the precursor solution and the solution is continuously stirred and heated to initiate a polymerization reaction to generate a P(AN-co-IA) copolymer, wherein the mass ratio of acrylonitrile to azobisisobutyronitrile in the precursor solution is 130:1, the stirring rate is 350 r / min, the stirring time is 20 h, the heating temperature is 60° C., and a polymer solution is obtained after the reaction is completed. Dimethyl sulfoxide is added to the polymer solution for dilution to obtain a spinning solution, and the mass fraction of the P(AN-co-IA) copolymer in the spinning solution is 13wt%;

[0183] (2) dissolving zirconium chloride, 1,4-phthalic acid and acetic acid in N,N-dimethylformamide in a mixing ratio of 1 mmol:1 mmol:3 mL:25 mL; mixing well and then performing ultrasonic dispersion at an ultrasonic power of 200 W for 20 min to obtain a precursor solution;

[0184] The precursor solution was transferred to a reactor, and the precursor solution was stirred and heated to react, the stirring rate was 200 r / min, the heating temperature was 120°C, and the reaction time was 25 h. After the reaction, the reaction product was washed and centrifuged in sequence, the centrifugal speed was 8000 r / min, the centrifugal time was 5 min, and the precipitate after centrifugation was dried, the drying temperature was 80°C, and the drying time was 24 h. After drying, UiO-66 powder was obtained;

[0185] (3) adding the UiO-66 powder obtained in step (2) to the spinning solution obtained in step (1), wherein the mass fraction of the UiO-66 powder in the spinning solution is 0.5wt%, and the mixture is stirred and heated to obtain a spinning solution, wherein the heating temperature is 70°C, the stirring rate is 300r / min, and the stirring time is 15h;

[0186] The spinning solution was electrospun to obtain a fiber felt with a thickness of 1 mm, wherein the diameter of the needle used in the electrospinning was 0.5 mm, the relative humidity of the environment was 35%, the ambient temperature was 40° C., the voltage was 20 kV, the propulsion speed was 1.5 mL / h, and the distance from the needle tip to the receiving screen was 10 cm;

[0187] (4) In an air atmosphere, the fiber felt is heated to 220° C. at a heating rate of 5° C. / min and kept at this temperature for 10 min. While heating and heating, the pressure in the oxidation furnace is increased to 0.12 MPa, and the pressure is maintained while keeping the temperature to complete the first pre-oxidation process;

[0188] Subsequently, the temperature was further increased to 230°C at a rate of 2°C / min and kept at that temperature for 10 minutes. While heating and increasing the temperature, the pressure in the oxidation furnace was continuously increased to 0.14 MPa, and the pressure was maintained while keeping the temperature to complete the second pre-oxidation process.

[0189] Subsequently, the temperature was further increased to 240°C at a rate of 2°C / min and kept at that temperature for 10 minutes. While heating and increasing the temperature, the pressure in the oxidation furnace was reduced to 0.12 MPa, and the pressure was maintained while keeping the temperature to complete the third pre-oxidation process.

[0190] Subsequently, the temperature was further heated to 245°C at a heating rate of 2°C / min and kept at that temperature for 10 minutes. While heating and heating, the pressure in the oxidation furnace was further reduced to 0.1 MPa, and the pressure was maintained while keeping the temperature, so as to complete the fourth pre-oxidation process.

[0191] Subsequently, the temperature was further increased to 250°C at a rate of 2°C / min and kept at that temperature for 10 minutes. While heating and increasing the temperature, the pressure in the oxidation furnace was increased to 0.12 MPa, and the pressure was maintained while keeping the temperature to complete the fifth pre-oxidation process.

[0192] Subsequently, the heating is continued to be carried out to 255°C at a heating rate of 2°C / min and the temperature is kept for 10 minutes. While heating and heating, the pressure in the oxidation furnace is continued to be increased to 0.13MPa, and the pressure is maintained while the temperature is kept to complete the sixth pre-oxidation process; after the insulation is completed, the pre-oxidation felt is cooled to room temperature to obtain;

[0193] (5) In a nitrogen atmosphere, the pre-oxidized felt obtained after pre-oxidation was heated to 600°C at a heating rate of 5°C / min and kept at that temperature for 6 minutes to complete the low-temperature carbonization process; then, the pre-oxidized felt was further heated to 1500°C at a heating rate of 5°C / min and kept at that temperature for 4 minutes to complete the high-temperature carbonization process; after the insulation was completed, the pre-oxidized felt was cooled to room temperature to obtain a carbon felt;

[0194] (6) Spraying a 1 wt% sucrose solution evenly on the carbon felt surface. The spraying amount of the sucrose solution on the carbon felt surface is 5 mL / m 2 After drying, the carbon felt sprayed with sucrose solution was placed in an activation furnace, and activation gas was introduced into the activation furnace. The volume flow ratio of argon, air and carbon dioxide in the activation gas was 1:0.5:0.2, and the flow rate of the activation gas was 80m 3 / h, heating the carbon felt to 900°C at a heating rate of 10°C / min and keeping the temperature for 25min, cooling it to room temperature after the end of the temperature keeping, completing the surface activation treatment, and obtaining activated carbon felt;

[0195] (7) Mix citric acid, ethylenediamine and deionized water to obtain a carbon source solution, wherein the molar ratio of citric acid to ethylenediamine is 1:18, and the mixing ratio of citric acid to deionized water is 1 g:100 mL. Add a 20 wt % sodium hydroxide solution to the carbon source solution to adjust its pH value to 9. Perform a hydrothermal reaction on the carbon source solution at a temperature of 170° C. for 15 h. After the reaction, centrifuge the reaction product at a speed of 8000 r / min for 20 min. Perform dialysis on the supernatant after centrifugation. The dialysis bag used for dialysis has a molecular weight cutoff of 800 Da. Perform freeze drying on the dialysis retentate at a temperature of -50° C. for 25 h. After freeze drying, obtain carbon dot powder.

[0196] (8) adding dopamine hydrochloride to Tris-HCl buffer, mixing evenly to obtain a dopamine solution with a concentration of 0.5 g / L, dispersing the carbon dot powder obtained in step (7) in the dopamine solution, wherein the mass ratio of the carbon dot powder to the dopamine hydrochloride in the dopamine solution is 1:1.3, and mixing evenly to obtain a modified carbon dot dispersion; soaking the activated carbon felt obtained in step (6) in the modified carbon dot dispersion, wherein the ratio of the activated carbon felt to the modified carbon dot dispersion is 1 g:100 mL, and after soaking for 5 hours, taking out the activated carbon felt and drying it, wherein the drying temperature is 70° C., the drying time is 5 hours, and after drying, high-temperature carbonization is performed at 850° C. for 1.5 hours to obtain a modified carbon felt;

[0197] (9) Mix manganese sulfate, potassium permanganate and deionized water to obtain a reaction solution, wherein the concentration of manganese sulfate in the reaction solution is 15 g / L, and the concentration of potassium permanganate is 110 g / L; transfer the reaction solution to a hydrothermal reactor, immerse the modified carbon felt obtained in step (8) in the reaction solution, wherein the ratio of the modified carbon felt to the reaction solution is 1 g:100 mL, and perform a hydrothermal reaction under stirring at a temperature of 130° C. for 20 h and a stirring rate of 400 r / min to in-situ generate δ-MnO2 on the surface of the modified carbon felt. After the reaction is completed, take out the modified carbon felt, rinse it and dry it at a temperature of 70° C. for 24 h to obtain an electrode carbon felt.

[0198] Figure 2 This is a scanning electron microscope image of the uncarbonized UIO-66 powder prepared in this embodiment. It can be seen from the figure that the UIO-66 powder prepared in this embodiment has a regular octahedral structure, a smooth surface, uniform particle size, and an average particle size between 400 and 500 nm.

[0199] Figure 3 This is a scanning electron microscope image of the carbonized UIO-66 powder in the activated carbon felt prepared in this embodiment. It can be seen from the figure that the carbonized UIO-66 powder basically maintains the original octahedral structure of the UIO-66 powder, but the surface of the carbonized UIO-66 powder is relatively rough, and the average particle size is between 250 and 300 nm. Compared with the uncarbonized UIO-66 powder, the particle size of the carbonized UIO-66 powder is slightly reduced.

[0200] Figure 4 This is a scanning electron microscope image of the fiber surface of the fiber felt prepared in this example. It can be seen from the image that a large amount of particles are evenly attached to the fiber surface, which is UIO-66 powder.

[0201] Figure 5 This is the infrared spectrum of the UIO-66 powder prepared in this example before and after carbonization. It can be seen from the figure that the characteristic peak of 1,4-phthalic acid of the UIO-66 powder after carbonization basically disappears, and the vibration peak of the Zr-O coordination bond changes significantly, converting into carbon-doped ZrO2 with a more stable structure.

[0202] Figure 6 and Figure 7 The scanning electron microscope images of the fiber surface of the electrode carbon felt prepared in this embodiment at different magnifications show that the in-situ synthesized δ-MnO2 is uniformly attached to the fiber surface of the modified carbon felt, and the δ-MnO2 as a whole is a cluster structure composed of nanosheets. This structure has a good interlayer gap, which is convenient for ion transport and charge transfer.

[0203] Figure 8 This is a transmission electron microscope image of the electrode carbon felt prepared in this example. It can be seen from the image that δ-MnO2 presents a multi-layer nanosheet structure.

[0204] Example 2

[0205] This embodiment provides a method for modifying preoxidized fiber felt to improve the performance of electrode carbon felt, such as Figure 1 As shown, the preoxidized fiber felt modification method specifically comprises the following steps:

[0206] (1) acrylonitrile, itaconic acid and dimethyl sulfoxide were mixed uniformly in a mass ratio of 46:1:212 to obtain a precursor solution, and the precursor solution was stirred and heated in a nitrogen atmosphere, wherein the stirring rate was 380 r / min, the stirring time was 28 min, and the heating temperature was 62° C.;

[0207] Subsequently, azobisisobutyronitrile is added to the precursor solution and the solution is continuously stirred and heated to initiate a polymerization reaction to generate a P(AN-co-IA) copolymer, wherein the mass ratio of acrylonitrile to azobisisobutyronitrile in the precursor solution is 132:1, the stirring rate is 380 r / min, the stirring time is 19.5 h, the heating temperature is 62° C., and a polymer solution is obtained after the reaction is completed. Dimethyl sulfoxide is added to the polymer solution for dilution to obtain a spinning solution, and the mass fraction of the P(AN-co-IA) copolymer in the spinning solution is 13.5 wt %;

[0208] (2) dissolving zirconium chloride, 1,4-phthalic acid and acetic acid in N,N-dimethylformamide in a mixing ratio of 1 mmol:1 mmol:3.5 mL:28 mL; mixing well and then performing ultrasonic dispersion at an ultrasonic power of 220 W for 18 min to obtain a precursor solution;

[0209] The precursor solution was transferred to a reactor, and the precursor solution was stirred and heated to react, the stirring rate was 220 r / min, the heating temperature was 122°C, and the reaction time was 24 h. After the reaction, the reaction product was washed and centrifuged in sequence, the centrifugal speed was 8200 r / min, the centrifugal time was 4.5 min, and the precipitate after centrifugation was dried, the drying temperature was 85°C, and the drying time was 21 h. After drying, UiO-66 powder was obtained;

[0210] (3) adding the UiO-66 powder obtained in step (2) to the spinning solution obtained in step (1), wherein the mass fraction of the UiO-66 powder in the spinning solution is 0.8wt%, and the mixture is stirred and heated to obtain a spinning solution, wherein the heating temperature is 72°C, the stirring rate is 320r / min, and the stirring time is 14h;

[0211] The spinning solution was electrospun to obtain a fiber felt with a thickness of 1.5 mm, wherein the diameter of the needle used in the electrospinning was 0.8 mm, the relative humidity of the environment was 38%, the ambient temperature was 38° C., the voltage was 22 kV, the propulsion speed was 1.8 mL / h, and the distance from the needle tip to the receiving screen was 12 cm;

[0212] (4) In an air atmosphere, the fiber felt is heated to 221° C. at a heating rate of 6° C. / min and kept at this temperature for 9.5 min. While heating and heating, the pressure in the oxidation furnace is increased to 0.122 MPa, and the pressure is maintained while keeping the temperature to complete the first pre-oxidation process;

[0213] Subsequently, the temperature was raised to 231°C at a rate of 3°C / min and kept at that temperature for 9.5 minutes. The pressure in the oxidation furnace was increased to 0.142 MPa while the temperature was raised. The pressure was maintained while the temperature was maintained to complete the second pre-oxidation process.

[0214] Subsequently, the temperature was further heated to 241°C at a heating rate of 3°C / min and kept at that temperature for 9.5 minutes. While heating and heating, the pressure in the oxidation furnace was reduced to 0.122 MPa, and the pressure was maintained while keeping the temperature to complete the third pre-oxidation process.

[0215] Subsequently, the temperature was further heated to 246°C at a heating rate of 3°C / min and kept at that temperature for 9.5 minutes. While heating and heating, the pressure in the oxidation furnace was further reduced to 0.102MPa. The pressure was maintained while keeping the temperature, so as to complete the fourth pre-oxidation process.

[0216] Subsequently, the temperature was further increased to 251°C at a rate of 3°C / min and kept at that temperature for 9.5 minutes. While heating and increasing the temperature, the pressure in the oxidation furnace was increased to 0.122 MPa. The pressure was maintained while the temperature was maintained to complete the fifth pre-oxidation process.

[0217] Subsequently, the heating was continued to 256°C at a heating rate of 3°C / min and kept at that temperature for 9.5 minutes. While heating and heating, the pressure in the oxidation furnace was continued to be increased to 0.132MPa, and the pressure was maintained while keeping the temperature to complete the sixth pre-oxidation process. After the end of the heat preservation, the pre-oxidation felt was cooled to room temperature to obtain the pre-oxidation felt.

[0218] (5) In a nitrogen atmosphere, the pre-oxidized felt obtained after pre-oxidation was heated to 620°C at a heating rate of 6°C / min and kept at this temperature for 5 minutes to complete the low-temperature carbonization process; then, the pre-oxidized felt was further heated to 1520°C at a heating rate of 6°C / min and kept at this temperature for 3.5 minutes to complete the high-temperature carbonization process; after the insulation was completed, the pre-oxidized felt was cooled to room temperature to obtain a carbon felt;

[0219] (6) Spraying a sucrose solution with a mass fraction of 1.2 wt% evenly on the surface of the carbon felt. The spraying amount of the sucrose solution on the surface of the carbon felt is 4.8 mL / m 2 After drying, the carbon felt sprayed with sucrose solution was placed in an activation furnace, and activation gas was introduced into the activation furnace. The volume flow ratio of argon, air and carbon dioxide in the activation gas was 1:0.52:0.22, and the flow rate of the activation gas was 90m 3 / h, heating the carbon felt to 920°C at a heating rate of 10.5°C / min and keeping the temperature for 22 minutes, cooling it to room temperature after the end of the heat preservation, completing the surface activation treatment, and obtaining activated carbon felt;

[0220] (7) Mix citric acid, ethylenediamine and deionized water to obtain a carbon source solution, wherein the molar ratio of citric acid to ethylenediamine is 1:18.5, and the mixing ratio of citric acid to deionized water is 1 g:105 mL. Add a sodium hydroxide solution with a mass fraction of 22 wt% to the carbon source solution to adjust its pH value to 8.8, and perform a hydrothermal reaction on the carbon source solution. The temperature of the hydrothermal reaction is 172° C. and the time of the hydrothermal reaction is 13 h. After the reaction, the reaction product is centrifuged at a speed of 8200 r / min and a centrifugation time of 18 min. The supernatant after centrifugal filtration is dialyzed. The molecular weight cutoff of the dialysis bag used for dialysis is 850 Da. The retentate is freeze-dried at a temperature of -52° C. and a time of 24 h. After freeze-drying, carbon dot powder is obtained.

[0221] (8) adding dopamine hydrochloride to Tris-HCl buffer, mixing evenly to obtain a dopamine solution with a concentration of 0.8 g / L, dispersing the carbon dot powder obtained in step (7) in the dopamine solution, wherein the mass ratio of the carbon dot powder to the dopamine hydrochloride in the dopamine solution is 1:1.35, and mixing evenly to obtain a modified carbon dot dispersion; soaking the activated carbon felt obtained in step (6) in the modified carbon dot dispersion, wherein the ratio of the activated carbon felt to the modified carbon dot dispersion is 1 g:105 mL, and after soaking for 6 hours, taking out the activated carbon felt and drying it, wherein the drying temperature is 72° C., the drying time is 4.5 hours, and after drying, high-temperature carbonization is performed at 880° C. for 1.2 hours to obtain a modified carbon felt;

[0222] (9) Mix manganese sulfate, potassium permanganate and deionized water to obtain a reaction solution, wherein the concentration of manganese sulfate in the reaction solution is 18 g / L, and the concentration of potassium permanganate is 112 g / L; transfer the reaction solution to a hydrothermal reactor, immerse the modified carbon felt obtained in step (8) in the reaction solution, wherein the ratio of the modified carbon felt to the reaction solution is 1 g:105 mL, and perform a hydrothermal reaction under stirring at a temperature of 135° C. for 18 h and a stirring rate of 420 r / min to in-situ generate δ-MnO2 on the surface of the modified carbon felt. After the reaction is completed, take out the modified carbon felt, rinse it and dry it at a temperature of 72° C. for 21 h to obtain an electrode carbon felt.

[0223] Example 3

[0224] This embodiment provides a method for modifying preoxidized fiber felt to improve the performance of electrode carbon felt, such as Figure 1 As shown, the preoxidized fiber felt modification method specifically comprises the following steps:

[0225] (1) acrylonitrile, itaconic acid and dimethyl sulfoxide were mixed uniformly in a mass ratio of 47:1:215 to obtain a precursor solution, and the precursor solution was stirred and heated in a nitrogen atmosphere, wherein the stirring rate was 400 r / min, the stirring time was 25 min, and the heating temperature was 65° C.;

[0226] Subsequently, azobisisobutyronitrile is added to the precursor solution and the mixture is continuously stirred and heated to initiate a polymerization reaction to generate a P(AN-co-IA) copolymer, wherein the mass ratio of acrylonitrile to azobisisobutyronitrile in the precursor solution is 135:1, the stirring rate is 400 r / min, the stirring time is 19 h, and the heating temperature is 65° C. After the reaction is completed, a polymer solution is obtained, and dimethyl sulfoxide is added to the polymer solution for dilution to obtain a spinning solution, wherein the mass fraction of the P(AN-co-IA) copolymer in the spinning solution is 14 wt %;

[0227] (2) dissolving zirconium chloride, 1,4-phthalic acid and acetic acid in N,N-dimethylformamide in a mixing ratio of 1 mmol:1 mmol:4 mL:30 mL; mixing well and then performing ultrasonic dispersion at an ultrasonic power of 250 W for 15 min to obtain a precursor solution;

[0228] The precursor solution was transferred to a reactor, and the precursor solution was stirred and heated to react, the stirring rate was 250 r / min, the heating temperature was 125°C, and the reaction time was 23 h. After the reaction, the reaction product was washed and centrifuged in sequence, the centrifugal speed was 8500 r / min, the centrifugal time was 4 min, and the precipitate after centrifugation was dried, the drying temperature was 90°C, and the drying time was 18 h. After drying, UiO-66 powder was obtained;

[0229] (3) adding the UiO-66 powder obtained in step (2) to the spinning solution obtained in step (1), wherein the mass fraction of the UiO-66 powder in the spinning solution is 1 wt%, and then stirring and heating to obtain a spinning solution, wherein the heating temperature is 75° C., the stirring rate is 350 r / min, and the stirring time is 13 h;

[0230] The spinning solution was electrospun to obtain a fiber felt with a thickness of 2 mm, wherein the diameter of the needle used in the electrospinning was 1 mm, the relative humidity of the environment was 40%, the ambient temperature was 35° C., the voltage was 25 kV, the propulsion speed was 2 mL / h, and the distance from the needle tip to the receiving screen was 15 cm;

[0231] (4) In an air atmosphere, the fiber felt is heated to 222° C. at a heating rate of 7° C. / min and kept at this temperature for 9 minutes. While heating and heating, the pressure in the oxidation furnace is increased to 0.125 MPa, and the pressure is maintained while keeping the temperature to complete the first pre-oxidation process;

[0232] Subsequently, the temperature was raised to 232°C at a rate of 3°C / min and kept at that temperature for 9 minutes. While heating and raising the temperature, the pressure in the oxidation furnace was increased to 0.145 MPa, and the pressure was maintained while keeping the temperature to complete the second pre-oxidation process.

[0233] Subsequently, the temperature was further heated to 242°C at a heating rate of 3°C / min and kept at that temperature for 9 minutes. While heating and heating, the pressure in the oxidation furnace was reduced to 0.125 MPa, and the pressure was maintained while keeping the temperature to complete the third pre-oxidation process.

[0234] Subsequently, the temperature was further heated to 247°C at a heating rate of 3°C / min and kept at that temperature for 9 minutes. While heating and heating, the pressure in the oxidation furnace was further reduced to 0.105MPa, and the pressure was maintained while keeping the temperature, so as to complete the fourth pre-oxidation process.

[0235] Subsequently, the temperature was further increased to 252°C at a rate of 3°C / min and kept at that temperature for 9 minutes. While the temperature was increased, the pressure in the oxidation furnace was increased to 0.125 MPa, and the pressure was maintained while the temperature was maintained to complete the fifth pre-oxidation process.

[0236] Subsequently, the heating was continued to 257°C at a heating rate of 3°C / min and kept at that temperature for 9 minutes. While heating and heating, the pressure in the oxidation furnace was continued to be increased to 0.135MPa, and the pressure was maintained while keeping the temperature to complete the sixth pre-oxidation process. After the end of the heat preservation, the pre-oxidation felt was cooled to room temperature to obtain the pre-oxidation felt.

[0237] (5) In a nitrogen atmosphere, the pre-oxidized felt obtained after the pre-oxidation was heated to 650°C at a heating rate of 7°C / min and kept at this temperature for 5 minutes to complete the low-temperature carbonization process; then, the pre-oxidized felt was further heated to 1550°C at a heating rate of 7°C / min and kept at this temperature for 3 minutes to complete the high-temperature carbonization process; after the insulation was completed, the pre-oxidized felt was cooled to room temperature to obtain a carbon felt;

[0238] (6) Spraying a 1.5 wt% sucrose solution evenly on the carbon felt surface, with a spraying amount of 4.5 mL / m 2 After drying, the carbon felt sprayed with sucrose solution was placed in an activation furnace, and activation gas was introduced into the activation furnace. The volume flow ratio of argon, air and carbon dioxide in the activation gas was 1:0.55:0.25, and the flow rate of the activation gas was 100m 3 / h, heating the carbon felt to 950°C at a heating rate of 11°C / min and keeping the temperature for 20min, cooling it to room temperature after the end of the temperature keeping, completing the surface activation treatment, and obtaining activated carbon felt;

[0239] (7) Mix citric acid, ethylenediamine and deionized water to obtain a carbon source solution, wherein the molar ratio of citric acid to ethylenediamine is 1:19, and the mixing ratio of citric acid to deionized water is 1 g:110 mL. Add a sodium hydroxide solution with a mass fraction of 25 wt % to the carbon source solution to adjust its pH value to 8.5. Perform a hydrothermal reaction on the carbon source solution at a temperature of 175° C. for 12 h. After the reaction, centrifuge the reaction product at a speed of 8500 r / min for 15 min. Perform dialysis on the supernatant after centrifugation. The dialysis bag used for dialysis has a molecular weight cutoff of 900 Da. Perform freeze drying on the retentate at a temperature of -55° C. for 23 h. After freeze drying, obtain carbon dot powder.

[0240] (8) adding dopamine hydrochloride to Tris-HCl buffer, mixing evenly to obtain a dopamine solution with a concentration of 1 g / L, dispersing the carbon dot powder obtained in step (7) in the dopamine solution, wherein the mass ratio of the carbon dot powder to the dopamine hydrochloride in the dopamine solution is 1:1.4, and mixing evenly to obtain a modified carbon dot dispersion; soaking the activated carbon felt obtained in step (6) in the modified carbon dot dispersion, wherein the ratio of the activated carbon felt to the modified carbon dot dispersion is 1 g:110 mL, and after soaking for 7 hours, taking out the activated carbon felt and drying it, wherein the drying temperature is 75° C., the drying time is 4 hours, and after drying, high-temperature carbonization is performed at 900° C. for 1 hour to obtain a modified carbon felt;

[0241] (9) Mix manganese sulfate, potassium permanganate and deionized water to obtain a reaction solution, wherein the concentration of manganese sulfate in the reaction solution is 20 g / L and the concentration of potassium permanganate is 115 g / L; transfer the reaction solution to a hydrothermal reactor, immerse the modified carbon felt obtained in step (8) in the reaction solution, wherein the ratio of the modified carbon felt to the reaction solution is 1 g:110 mL, and perform a hydrothermal reaction under stirring at a temperature of 140° C. for 17 h and a stirring rate of 450 r / min to in-situ generate δ-MnO2 on the surface of the modified carbon felt. After the reaction is completed, take out the modified carbon felt, rinse it and dry it at a temperature of 75° C. for 18 h to obtain an electrode carbon felt.

[0242] Example 4

[0243] This embodiment provides a method for modifying preoxidized fiber felt to improve the performance of electrode carbon felt, such as Figure 1 As shown, the preoxidized fiber felt modification method specifically comprises the following steps:

[0244] (1) acrylonitrile, itaconic acid and dimethyl sulfoxide were mixed uniformly in a mass ratio of 48:1:218 to obtain a precursor solution, and the precursor solution was stirred and heated in a nitrogen atmosphere, wherein the stirring rate was 420 r / min, the stirring time was 22 min, and the heating temperature was 68° C.;

[0245] Subsequently, azobisisobutyronitrile is added to the precursor solution and the mixture is continuously stirred and heated to initiate a polymerization reaction to generate a P(AN-co-IA) copolymer, wherein the mass ratio of acrylonitrile to azobisisobutyronitrile in the precursor solution is 138:1, the stirring rate is 420 / min, the stirring time is 18.5h, the heating temperature is 68°C, and a polymer solution is obtained after the reaction is completed. Dimethyl sulfoxide is added to the polymer solution for dilution to obtain a spinning solution, and the mass fraction of the P(AN-co-IA) copolymer in the spinning solution is 14.5wt%;

[0246] (2) dissolving zirconium chloride, 1,4-phthalic acid and acetic acid in N,N-dimethylformamide in a mixing ratio of 1 mmol:1 mmol:4.5 mL:32 mL, mixing well, and performing ultrasonic dispersion at an ultrasonic power of 280 W for 12 min to obtain a precursor solution;

[0247] The precursor solution was transferred to a reactor, and the precursor solution was stirred and heated to react, the stirring rate was 280 r / min, the heating temperature was 128°C, and the reaction time was 21 h. After the reaction, the reaction product was washed and centrifuged in sequence, the centrifugal speed was 8800 r / min, the centrifugal time was 3.5 min, and the precipitate after centrifugation was dried, the drying temperature was 95°C, and the drying time was 15 h. After drying, UiO-66 powder was obtained;

[0248] (3) adding the UiO-66 powder obtained in step (2) to the spinning solution obtained in step (1), wherein the mass fraction of the UiO-66 powder in the spinning solution is 1.2 wt %, and the mixture is stirred and heated to obtain a spinning solution, wherein the heating temperature is 78° C., the stirring rate is 380 r / min, and the stirring time is 12 h;

[0249] The spinning solution was electrospun to obtain a fiber felt with a thickness of 2.5 mm, wherein the diameter of the needle used in the electrospinning was 1.2 mm, the relative humidity of the environment was 42%, the ambient temperature was 32° C., the voltage was 28 kV, the propulsion speed was 2.2 mL / h, and the distance from the needle tip to the receiving screen was 18 cm;

[0250] (4) In an air atmosphere, the fiber felt is heated to 223° C. at a heating rate of 8° C. / min and kept at this temperature for 8.5 min. While heating and heating, the pressure in the oxidation furnace is increased to 0.128 MPa, and the pressure is maintained while keeping the temperature to complete the first pre-oxidation process;

[0251] Subsequently, the temperature was further increased to 233°C at a rate of 4°C / min and kept at that temperature for 8.5 minutes. While heating and increasing the temperature, the pressure in the oxidation furnace was continuously increased to 0.148 MPa. The pressure was maintained while the temperature was maintained to complete the second pre-oxidation process.

[0252] Subsequently, the temperature was further heated to 243°C at a heating rate of 4°C / min and kept at that temperature for 8.5 minutes. While heating and heating, the pressure in the oxidation furnace was reduced to 0.128 MPa, and the pressure was maintained while keeping the temperature to complete the third pre-oxidation process.

[0253] Subsequently, the temperature was further heated to 248°C at a heating rate of 4°C / min and kept at that temperature for 8.5 minutes. While heating and heating, the pressure in the oxidation furnace was further reduced to 0.108 MPa. The pressure was maintained while keeping the temperature, so as to complete the fourth pre-oxidation process.

[0254] Subsequently, the temperature was further increased to 253°C at a rate of 4°C / min and kept at that temperature for 8.5 minutes. While heating and increasing the temperature, the pressure in the oxidation furnace was increased to 0.128 MPa, and the pressure was maintained while keeping the temperature to complete the fifth pre-oxidation process.

[0255] Subsequently, the heating was continued to 258°C at a heating rate of 4°C / min and kept at that temperature for 8.5 minutes. While heating and heating, the pressure in the oxidation furnace was continued to be increased to 0.138MPa, and the pressure was maintained while keeping the temperature to complete the sixth pre-oxidation process. After the end of the heat preservation, the pre-oxidation felt was cooled to room temperature to obtain the pre-oxidation felt.

[0256] (5) In a nitrogen atmosphere, the pre-oxidized felt obtained after pre-oxidation was heated to 680°C at a heating rate of 7°C / min and kept at this temperature for 4 minutes to complete the low-temperature carbonization process; then, the pre-oxidized felt was further heated to 1580°C at a heating rate of 7°C / min and kept at this temperature for 2.5 minutes to complete the high-temperature carbonization process; after the insulation was completed, the pre-oxidized felt was cooled to room temperature to obtain a carbon felt;

[0257] (6) Spraying a sucrose solution with a mass fraction of 1.8 wt% evenly on the surface of the carbon felt. The spraying amount of the sucrose solution on the surface of the carbon felt is 4.2 mL / m 2 After drying, the carbon felt sprayed with sucrose solution was placed in an activation furnace, and activation gas was introduced into the activation furnace. The volume flow ratio of argon, air and carbon dioxide in the activation gas was 1:0.58:0.28, and the flow rate of the activation gas was 110m 3 / h, heating the carbon felt to 980°C at a heating rate of 11.5°C / min and keeping the temperature for 18 minutes, cooling it to room temperature after the end of the heat preservation, completing the surface activation treatment, and obtaining activated carbon felt;

[0258] (7) Mix citric acid, ethylenediamine and deionized water to obtain a carbon source solution, wherein the molar ratio of citric acid to ethylenediamine is 1:19.5, and the mixing ratio of citric acid to deionized water is 1 g:115 mL. Add a sodium hydroxide solution with a mass fraction of 28 wt% to the carbon source solution to adjust its pH value to 8.2, and perform a hydrothermal reaction on the carbon source solution. The temperature of the hydrothermal reaction is 178° C. and the time of the hydrothermal reaction is 11 h. After the reaction, the reaction product is centrifuged at a speed of 8800 r / min and a centrifugation time of 12 min. The supernatant after centrifugal filtration is dialyzed. The molecular weight cutoff of the dialysis bag used for dialysis is 950 Da. The dialysis retentate is freeze-dried at a temperature of -58° C. and a freeze-drying time of 21 h. After freeze-drying, carbon dot powder is obtained;

[0259] (8) adding dopamine hydrochloride to Tris-HCl buffer, mixing evenly to obtain a dopamine solution with a concentration of 1.2 g / L, dispersing the carbon dot powder obtained in step (7) in the dopamine solution, wherein the mass ratio of the carbon dot powder to the dopamine hydrochloride in the dopamine solution is 1:1.45, and mixing evenly to obtain a modified carbon dot dispersion; soaking the activated carbon felt obtained in step (6) in the modified carbon dot dispersion, wherein the ratio of the activated carbon felt to the modified carbon dot dispersion is 1 g:115 mL, and after soaking for 8 hours, taking out the activated carbon felt and drying it, wherein the drying temperature is 78° C., the drying time is 3.5 hours, and after drying, high-temperature carbonization is performed at 920° C. for 0.8 hours to obtain a modified carbon felt;

[0260] (9) Mix manganese sulfate, potassium permanganate and deionized water to obtain a reaction solution, wherein the concentration of manganese sulfate in the reaction solution is 22 g / L, and the concentration of potassium permanganate is 118 g / L; transfer the reaction solution to a hydrothermal reactor, immerse the modified carbon felt obtained in step (8) in the reaction solution, wherein the ratio of the modified carbon felt to the reaction solution is 1 g:115 mL, and perform a hydrothermal reaction under stirring at a temperature of 145° C. for 16 h and a stirring rate of 480 r / min to in-situ generate δ-MnO2 on the surface of the modified carbon felt. After the reaction is completed, take out the modified carbon felt, rinse it and dry it at a temperature of 78° C. for 15 h to obtain an electrode carbon felt.

[0261] Example 5

[0262] This embodiment provides a method for modifying preoxidized fiber felt to improve the performance of electrode carbon felt, such as Figure 1 As shown, the preoxidized fiber felt modification method specifically comprises the following steps:

[0263] (1) acrylonitrile, itaconic acid and dimethyl sulfoxide were mixed uniformly in a mass ratio of 50:1:220 to obtain a precursor solution, and the precursor solution was stirred and heated in a nitrogen atmosphere, wherein the stirring rate was 450 r / min, the stirring time was 20 min, and the heating temperature was 70° C.;

[0264] Subsequently, azobisisobutyronitrile is added to the precursor solution and the solution is continuously stirred and heated to initiate a polymerization reaction to generate a P(AN-co-IA) copolymer, wherein the mass ratio of acrylonitrile to azobisisobutyronitrile in the precursor solution is 140:1, the stirring rate is 450 r / min, the stirring time is 18 h, the heating temperature is 70° C., and a polymer solution is obtained after the reaction is completed. Dimethyl sulfoxide is added to the polymer solution for dilution to obtain a spinning solution, and the mass fraction of the P(AN-co-IA) copolymer in the spinning solution is 15wt%;

[0265] (2) dissolving zirconium chloride, 1,4-phthalic acid and acetic acid in N,N-dimethylformamide in a mixing ratio of 1 mmol:1 mmol:5 mL:35 mL; mixing well and then performing ultrasonic dispersion at an ultrasonic power of 300 W for 10 min to obtain a precursor solution;

[0266] The precursor solution was transferred to a reactor, and the precursor solution was stirred and heated to react, the stirring rate was 300 r / min, the heating temperature was 120°C, and the reaction time was 20 h. After the reaction, the reaction product was washed and centrifuged in sequence, the centrifugal speed was 9000 r / min, the centrifugal time was 3 min, and the precipitate after centrifugation was dried, the drying temperature was 100°C, and the drying time was 12 h. After drying, UiO-66 powder was obtained;

[0267] (3) adding the UiO-66 powder obtained in step (2) to the spinning solution obtained in step (1), wherein the mass fraction of the UiO-66 powder in the spinning solution is 1.5wt%, and the mixture is stirred and heated to obtain a spinning solution, wherein the heating temperature is 80°C, the stirring rate is 400r / min, and the stirring time is 10h;

[0268] The spinning solution was electrospun to obtain a fiber felt with a thickness of 3 mm, wherein the diameter of the needle used in the electrospinning was 1.5 mm, the relative humidity of the environment was 45%, the ambient temperature was 30° C., the voltage was 30 kV, the propulsion speed was 2.5 mL / h, and the distance from the needle tip to the receiving screen was 20 cm;

[0269] (4) In an air atmosphere, the fiber felt is heated to 225° C. at a heating rate of 10° C. / min and kept at this temperature for 8 min. While heating and heating, the pressure in the oxidation furnace is increased to 0.13 MPa, and the pressure is maintained while keeping the temperature to complete the first pre-oxidation process;

[0270] Subsequently, the temperature was raised to 235°C at a rate of 5°C / min and kept at that temperature for 8 minutes. While heating and raising the temperature, the pressure in the oxidation furnace was continuously increased to 0.15 MPa. The pressure was maintained while keeping the temperature, so as to complete the second pre-oxidation process.

[0271] Subsequently, the temperature was further heated to 245°C at a heating rate of 5°C / min and kept at that temperature for 8 minutes. While heating and heating, the pressure in the oxidation furnace was reduced to 0.13 MPa, and the pressure was maintained while keeping the temperature to complete the third pre-oxidation process.

[0272] Subsequently, the temperature was further heated to 250°C at a heating rate of 5°C / min and kept at that temperature for 8 minutes. While heating and heating, the pressure in the oxidation furnace was further reduced to 0.11 MPa. The pressure was maintained while keeping the temperature, so as to complete the fourth pre-oxidation process.

[0273] Subsequently, the temperature was further increased to 255°C at a rate of 5°C / min and kept at that temperature for 8 minutes. While the temperature was increased, the pressure in the oxidation furnace was increased to 0.13 MPa. The pressure was maintained while the temperature was maintained to complete the fifth pre-oxidation process.

[0274] Subsequently, the heating is continued to 260°C at a heating rate of 5°C / min and the temperature is kept for 8 minutes. While heating and heating, the pressure in the oxidation furnace is continued to be increased to 0.14MPa, and the pressure is maintained while the temperature is kept to complete the sixth pre-oxidation process; after the insulation is completed, the pre-oxidation felt is cooled to room temperature to obtain;

[0275] (5) In a nitrogen atmosphere, the pre-oxidized felt obtained after pre-oxidation was heated to 700°C at a heating rate of 8°C / min and kept at this temperature for 3 minutes to complete the low-temperature carbonization process; then, the pre-oxidized felt was further heated to 1600°C at a heating rate of 8°C / min and kept at this temperature for 2 minutes to complete the high-temperature carbonization process; after the insulation was completed, the pre-oxidized felt was cooled to room temperature to obtain a carbon felt;

[0276] (6) Spray 2 wt% sucrose solution evenly on the surface of the carbon felt. The spraying amount of the sucrose solution on the surface of the carbon felt is 4 mL / m 2 After drying, the carbon felt sprayed with sucrose solution was placed in an activation furnace, and activation gas was introduced into the activation furnace. The volume flow ratio of argon, air and carbon dioxide in the activation gas was 1:0.6:0.3, and the flow rate of the activation gas was 120m 3 / h, heating the carbon felt to 1000°C at a heating rate of 12°C / min and keeping the temperature for 15 minutes, cooling it to room temperature after the end of the heat preservation, completing the surface activation treatment, and obtaining activated carbon felt;

[0277] (7) Mix citric acid, ethylenediamine and deionized water to obtain a carbon source solution, wherein the molar ratio of citric acid to ethylenediamine is 1:20, and the mixing ratio of citric acid to deionized water is 1 g:120 mL. Add a 30 wt % sodium hydroxide solution to the carbon source solution to adjust its pH value to 8. Perform a hydrothermal reaction on the carbon source solution at a temperature of 180° C. for 10 h. After the reaction, centrifuge the reaction product at a speed of 9000 r / min for 10 min. Perform dialysis on the supernatant after centrifugation. The dialysis bag used for dialysis has a molecular weight cutoff of 1000 Da. The dialysis retentate is freeze-dried at a temperature of -60° C. for 20 h. After freeze-drying, carbon dot powder is obtained.

[0278] (8) adding dopamine hydrochloride to Tris-HCl buffer, mixing evenly to obtain a dopamine solution with a concentration of 1.5 g / L, dispersing the carbon dot powder obtained in step (7) in the dopamine solution, the mass ratio of the carbon dot powder to the dopamine hydrochloride in the dopamine solution being 1:1.5, and mixing evenly to obtain a modified carbon dot dispersion; soaking the activated carbon felt obtained in step (6) in the modified carbon dot dispersion, the ratio of the activated carbon felt to the modified carbon dot dispersion being 1 g:120 mL, taking out the activated carbon felt after soaking for 10 hours and drying it at a drying temperature of 80° C. for 3 hours, and then carbonizing it at a high temperature of 950° C. for 0.5 hours to obtain a modified carbon felt;

[0279] (9) Mix manganese sulfate, potassium permanganate and deionized water to obtain a reaction solution, wherein the concentration of manganese sulfate in the reaction solution is 25 g / L, and the concentration of potassium permanganate is 120 g / L; transfer the reaction solution to a hydrothermal reactor, immerse the modified carbon felt obtained in step (8) in the reaction solution, wherein the ratio of the modified carbon felt to the reaction solution is 1 g:120 mL, and perform a hydrothermal reaction under stirring at a temperature of 150° C. for 15 h and a stirring rate of 500 r / min to generate δ-MnO2 in situ on the surface of the modified carbon felt. After the reaction is completed, take out the modified carbon felt, rinse it and dry it at a temperature of 80° C. for 12 h to obtain an electrode carbon felt.

[0280] Comparative Example 1

[0281] This comparative example provides a pre-oxidized fiber felt modification method for improving the performance of electrode carbon felt. The difference from Example 1 is that in step (3), the mass fraction of UiO-66 powder in the spinning solution is adjusted to 0.3wt%, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0282] Comparative Example 2

[0283] This comparative example provides a pre-oxidized fiber felt modification method for improving the performance of electrode carbon felt. The difference from Example 1 is that in step (3), the mass fraction of UiO-66 powder in the spinning solution is adjusted to 1.8wt%, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0284] Comparative Example 3

[0285] This comparative example provides a method for modifying pre-oxidized fiber felt for improving the performance of electrode carbon felt. The difference from Example 1 is that in step (3), the diameter of the needle used in electrospinning is adjusted to 0.2 mm, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0286] Comparative Example 4

[0287] This comparative example provides a method for modifying pre-oxidized fiber felt for improving the performance of electrode carbon felt. The difference from Example 1 is that in step (3), the diameter of the needle used in electrospinning is adjusted to 1.8 mm, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0288] Comparative Example 5

[0289] This comparative example provides a preoxidation fiber felt modification method for improving the performance of electrode carbon felt. The difference from Example 1 is that the preoxidation process is adjusted from a six-stage gradient temperature rise preoxidation process to a four-stage gradient temperature rise preoxidation process. At the same time, no pressure is applied to the preoxidation furnace. Specifically, the method includes the following steps:

[0290] (1) In an air atmosphere, heating the fiber felt to 230° C. at a heating rate of 8° C. / min and keeping the temperature for 15 min to complete a first pre-oxidation process;

[0291] (2) continuing to heat to 240°C at a heating rate of 5°C / min and keeping the temperature for 15 min to complete the second pre-oxidation process;

[0292] (3) continuing to heat to 250°C at a heating rate of 5°C / min and keeping the temperature for 15 min to complete the third pre-oxidation process;

[0293] (4) Continue heating to 265° C. at a heating rate of 5° C. / min and keep the temperature for 15 min to complete the fourth pre-oxidation process to obtain a pre-oxidation felt.

[0294] Other process parameters and operation steps are exactly the same as those in Example 1.

[0295] Comparative Example 6

[0296] This comparative example provides a pre-oxidation fiber felt modification method for improving the performance of electrode carbon felt. The difference from Example 1 is that during the pre-oxidation process, no pressurization is applied to the oxidation furnace, and the entire pre-oxidation process is carried out under normal pressure. Other process parameters and operating steps are exactly the same as those in Example 1.

[0297] Comparative Example 7

[0298] This comparative example provides a pre-oxidized fiber felt modification method for improving the performance of electrode carbon felt. The difference from Example 1 is that in step (8), the mass ratio of carbon dot powder to dopamine hydrochloride in the dopamine solution is adjusted to 1:1, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0299] Comparative Example 8

[0300] This comparative example provides a pre-oxidized fiber felt modification method for improving the performance of electrode carbon felt. The difference from Example 1 is that in step (8), the mass ratio of carbon dot powder to dopamine hydrochloride in the dopamine solution is adjusted to 1:1.8, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0301] Comparative Example 9

[0302] The present comparative example provides a preoxidized fiber felt modification method for improving the performance of electrode carbon felt, which differs from Example 1 in that step (2), step (7), step (8) and step (9) are omitted, that is: first, the spinning solution prepared in step (1) is directly subjected to electrospinning without adding UiO-66 powder thereto, and the preparation process of the spinning solution and the process parameters of the electrospinning are exactly the same as those in Example 1; then, the fiber felt obtained by electrospinning is subjected to preoxidation, carbonization and surface activation treatment in sequence, and the process parameters and operation steps of the preoxidation, carbonization and surface activation treatment are exactly the same as those in Example 1; finally, the activated carbon felt obtained after the surface activation treatment is directly used as the electrode carbon felt without being subjected to surface modification treatment.

[0303] Electrochemical tests and full battery tests were performed on the electrode carbon felts prepared in Examples 1-5 and Comparative Examples 1-9.

[0304] The electrochemical tests included cyclic voltammetry and electrochemical impedance spectroscopy. The test was conducted using a Reference 3000 electrochemical workstation in a three-electrode system, with a saturated calomel electrode and platinum sheet as the reference electrode (RE) and auxiliary electrode (CE), respectively. The positive electrolyte used was 0.1 M VO 2++2M H2SO4 solution, the negative electrode electrolyte uses 0.1M V 3+ +2M H2SO4 solution, cut the electrode carbon felts prepared in Examples 1-5 and Comparative Examples 1-9 into a size of 1.0 cm×1.0 cm, put them into a polytetrafluoroethylene mold, and use them as working electrodes (WE) for electrochemical performance testing.

[0305] (1) Cyclic voltammetry test

[0306] As a common electrochemical research method, cyclic voltammetry is often used to study the kinetic parameters, properties and mechanisms of electrode reaction processes. The reversibility of the reaction of the electrode carbon felt is determined by the symmetry of the oxidation peak and reduction peak in the cyclic voltammetry curve obtained by the test and the peak potential difference between the two peaks. At the same time, the electrochemical activity on the electrode carbon felt is determined by the redox peak current density value.

[0307] The test range of positive electrode reaction is 0.5~1.2V, using 1mVs -1 The voltage sweep rate was set to measure the cyclic voltammetry curve of the third cycle. The cyclic voltammetry curves of the positive electrode reactions of Example 1 and Comparative Example 9 are shown in FIG. Fig. 9 As can be seen from the figure, the ΔE of Example 1 and Comparative Example 9 are 145mV and 250mV respectively. Compared with Comparative Example 1, the ΔE of Example 1 is reduced by 105mV, which shows that the reversibility of the electrode carbon felt can be greatly improved by adding UiO-66 powder to the spinning solution and performing carbon-nitrogen dual doping and in-situ modification of δ-MnO2 on the activated carbon felt. At the same time, it can be clearly found that compared with Comparative Example 9, the current density of the oxidation peak and the reduction peak in the cyclic voltammetry curve of Example 1 is significantly improved, which shows that the electrochemical activity of the electrode carbon felt is significantly enhanced. This is because the introduction of UiO-66 powder and δ-MnO2 with a high specific surface area greatly increases the reaction active sites, which plays a very favorable role in enhancing the electrochemical properties of the electrode carbon felt.

[0308] The test range of negative electrode reaction is -0.7~-0.3V, using 1mVs -1 The voltage sweep rate was set to measure the cyclic voltammetry curve of the 10th cycle. The cyclic voltammetry curves of the negative electrode reactions of Example 1 and Comparative Example 9 are shown in FIG. Fig.10 As can be seen from the figure, there is no reduction peak in the cyclic voltammetry curve of Comparative Example 9, and the peak current of the oxidation peak of Comparative Example 9 is 20 mA cm -2 , while the peak current of the oxidation peak of Example 1 is 29.51 mA cm -2 This shows that the electrochemical activity and electrochemical reversibility of the electrode carbon felt are significantly enhanced. This is because the introduction of UiO-66 powder and δ-MnO2 with high specific surface area greatly increases the reaction active sites, which plays a very favorable role in enhancing the electrochemical properties of the electrode carbon felt.

[0309] (2) Electrochemical impedance spectroscopy

[0310] In order to visually observe the reaction kinetics before and after the carbon felt treatment, the present invention conducted an electrochemical impedance test on the electrode carbon felt prepared in Example 1 and Comparative Example 9. Electrochemical impedance test is a common electrochemical test technology, which is mainly used to measure the impedance effect of the system under test under the frequency of the AC potential. The test principle is to apply a small amplitude AC potential wave of different frequencies to the electrochemical system, so that the system generates a responsive current signal, analyze the impedance of the electrode according to the relationship between the two, and then analyze the size of each component according to the equivalent circuit model, use the electrochemical meaning of the components in the circuit to analyze the kinetic process and mechanism of the electrode system, and estimate the kinetic parameters of the electrode system through the parameter values ​​of the components.

[0311] Electrochemical impedance spectroscopy Figure 1 It is generally composed of a semicircle and a straight line. The left side of the semicircle is the high-frequency area, and the intersection of the high-frequency area and the real axis is the ohmic resistance in the solution (R s ) reflects the resistance to ion migration in the solution, simulates the conduction process of ions in the solution, and is regarded as the bulk resistance of the solution; the right side of the semicircle is the low-frequency area, and the diameter of the semicircle is the electrochemical reaction resistance (R ct ), the appearance of this impedance indicates that the reaction process is mainly controlled by electrochemical polarization, and the reaction has a certain degree of irreversibility. The larger the diameter of the semicircle, that is, the larger the electrochemical reaction resistance, the worse the irreversibility of the reaction.

[0312] The frequency range of the electrochemical impedance test is 100kHz-10mHz, and the disturbance signal is 5mV. In the test of the positive electrode EIS impedance spectrum, the starting voltage is 0.70V, and in the test of the negative electrode EIS impedance spectrum, the starting voltage is -0.40V.

[0313] The electrochemical impedance spectra of the positive electrode reactions of Example 1 and Comparative Example 9 are shown in Fig.11 As shown in the figure, it can be seen that the semicircle diameter of the electrochemical impedance spectrum of Example 1 is much smaller than that of Comparative Example 9. ct is 76.8Ω, while R ct The value is 13.2Ω, which indicates that in the electrochemical mass transfer process, the electrode carbon felt prepared in Example 1 has a better catalytic effect on the positive electrode reaction and can effectively improve VO 2+ / VO2 + The electrochemical reaction rate of the positive electrode reaction couple.

[0314] The electrochemical impedance spectra of the positive and negative electrode reactions of Example 1 and Comparative Example 9 are as follows: Fig.12As shown in the figure, it can be seen that the semicircle diameter of the electrochemical impedance spectrum of Example 1 is much smaller than that of Comparative Example 9. ct is 4Ω, R of Example 1 ct 1.5Ω, which shows that in the electrochemical mass transfer process, the electrode carbon felt prepared in Example 1 has a better catalytic effect on the negative electrode reaction and can effectively improve V 3+ / V 2+ The electrochemical reaction rate of the negative electrode reaction couple.

[0315] The R of the electrode carbon felts prepared in other embodiments and comparative examples ct See Table 1.

[0316] The electrode carbon felts prepared in Examples 1-5 and Comparative Examples 1-9 were assembled into an all-vanadium liquid flow battery and a single cell test was performed. In a specific embodiment of the present invention, the test current collector of the single cell is a graphite plate, the positive and negative electrodes are separated by an ion exchange membrane, a gasket is used for sealing, the various parts are assembled and compacted with bolts, a peristaltic pump is used to provide power, and the electrolyte circulates in the battery at a uniform flow rate of 60 mL / min. The ion exchange membrane is a Nafion115 membrane with a size of 7.0 cm×7.0 cm. The starting valence of the positive and negative electrolytes is 1.5 M V 3.5+ +2M H2SO4 mixed solution, the volume is 50mL, the electrode is the electrode carbon felt prepared by Example 1-5 and Comparative Example 1-9, the size is 5.0cm×5.0cm×0.5cm.

[0317] The assembled single cell is charged at 50-300 mA cm -2 The charge and discharge tests were carried out within the current density range of 50 mA cm -2 , and get Fig.13 The energy efficiency diagram at different current densities is shown in the figure. It can be seen from the figure that at 150mA·cm -2 At the current density of 200 mA·cm, the energy efficiency of Example 1 is improved by 7.7% compared with that of Comparative Example 9. -2 The energy efficiency of Example 1 is improved by 9.2% compared with that of Comparative Example 9 at a current density of 300 mA·cm -2 ), the energy efficiency of Example 1 can reach 53.91%, which shows that the electrode carbon felt prepared in Example 1 has high electrochemical activity. -2 ) after 4 cycles of charge and discharge, and then restored to 150mA·cm -2 When charging and discharging are performed at a current density of 1.50 Å, the energy efficiency of Example 1 can be restored to 71.58%, which indicates that the electrode carbon felt prepared in Example 1 has good stability.

[0318] The single cell assembled with the electrode carbon felt provided in other embodiments and comparative examples has a current of 150 mA·cm -2 The energy efficiency at different current densities is shown in Table 1.

[0319] The assembled single cell was charged at 150 mA cm -2 The charge and discharge test was performed for 300 cycles at the current density. The discharge capacity retention rate of the single cell after 300 cycles was calculated based on the discharge capacity of the first cycle and the discharge capacity of the 300th cycle. The test results are shown in Table 1.

[0320] Table 1 Performance test results of single cells assembled with electrode carbon felt provided in the examples and comparative examples

[0321]

[0322] It can be seen from the data in Table 1 that the electrochemical reaction resistance of the electrode carbon felt prepared in Examples 1-5 of the present invention is much lower than that of the comparative examples 1-9, while the energy efficiency and cycle capacity retention rate are much higher than those of the comparative examples 1-9, which indicates that the electrode carbon felt prepared in the present invention has excellent electrochemical properties.

[0323] From the test results of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the electrochemical reaction resistance of the electrode carbon felt prepared in Comparative Example 1 and Comparative Example 2 is higher than that in Example 1, and the energy efficiency and cycle capacity retention rate are lower than that in Example 1. This is because the amount of UiO-66 powder added in Comparative Example 1 is too small, and an effective and continuous electrolyte ion transmission channel cannot be formed, resulting in a high energy required for ion transmission, which in turn affects the various electrochemical properties of the electrode carbon felt. In Comparative Example 2, the amount of UiO-66 powder added is too much, and the UiO-66 powder has obvious agglomeration on the fiber surface and inside, which affects the transmission of electrolyte ions and also affects the various electrochemical properties of the electrode carbon felt.

[0324] It can be seen from the test results of Example 1, Comparative Example 3 and Comparative Example 4 that the electrochemical reaction resistance of the electrode carbon felt prepared in Comparative Example 3 and Comparative Example 4 is higher than that in Example 1, and the energy efficiency and cycle capacity retention rate are lower than that in Example 1. This is because the needle diameter in Comparative Example 3 is smaller, the fibers obtained by spinning are thinner, and the mechanical properties of the fibers after carbonization are lower, which in turn affects the various electrochemical properties of the electrode carbon felt. In Comparative Example 4, the needle diameter is larger, and the fibers obtained by spinning are thicker. During the pre-oxidation process, the diffusion distance of oxygen is too long, resulting in incomplete oxidation reaction of the fiber core, resulting in an obvious skin-core structure. During the subsequent carbonization process, the lower oxygen content in the core causes a large number of small molecules to escape, thereby generating defects such as voids and holes in the fiber core. The mechanical properties of the carbonized fibers are lower, which in turn affects the various electrochemical properties of the electrode carbon felt.

[0325] It can be seen from the test results of Example 1 and Comparative Example 5 that the electrochemical reaction resistance of the electrode carbon felt prepared in Comparative Example 5 is higher than that in Example 1, and the energy efficiency and cycle capacity retention rate are lower than those in Example 1. This shows that compared with the four-stage gradient heating process adopted in Comparative Example 5, the six-stage gradient heating process adopted in Example 1 is more beneficial to the performance improvement of the pre-oxidized fiber. The fiber is pre-oxidized by six-stage gradient heating, and the pre-oxidation reaction is divided into more stages by increasing the number of temperature gradients. The pre-oxidation temperature can be effectively dispersed, and the starting temperature and the ending temperature are lowered. At the same time, it is also equivalent to reducing the heating rate, which plays a role in alleviating the concentrated heat release of the reaction, thereby greatly reducing the structural defects caused by concentrated heat release.

[0326] It can be seen from the test results of Example 1 and Comparative Example 6 that the electrochemical reaction resistance of the electrode carbon felt prepared in Comparative Example 6 is higher than that of Example 1, and the energy efficiency and cycle capacity retention rate are lower than those of Example 1. This shows that by applying a certain pressure to the oxidation furnace during the pre-oxidation process, the structure of the pre-oxidized fiber can be effectively optimized, so that the internal structure of the pre-oxidized fiber is more perfect, which lays the foundation for the subsequent modification effect. By applying different pressures at different pre-oxidation stages, the diffusion power of oxygen into the fiber is increased, which can effectively improve and prevent the appearance of the skin-core structure, bring direct positive effects on the improvement of the mechanical properties of the pre-oxidized fiber, and indirectly promote the improvement of the electrochemical properties of the electrode carbon felt.

[0327] It can be seen from the test results of Example 1, Comparative Example 7 and Comparative Example 8 that the electrochemical reaction resistance of the electrode carbon felt prepared in Comparative Example 7 and Comparative Example 8 is higher than that in Example 1, and the energy efficiency and cycle capacity retention rate are lower than that in Example 1. This is because the amount of dopamine hydrochloride added in Comparative Example 7 is too low, and the proportion of carbon dot powder added is correspondingly too high. The excess carbon dots will cover the clustered lamellar structure of δ-MnO2, blocking the pores and gaps of δ-MnO2, making it difficult for electrolyte ions to diffuse into the gaps of δ-MnO2, resulting in an excessively large ineffective dead volume of δ-MnO2, which hinders the diffusion process of electrolyte ions and ultimately leads to a decrease in the electrochemical performance of the electrode carbon felt. However, in Comparative Example 8, the amount of dopamine hydrochloride added is too high, and the proportion of carbon dot powder added is correspondingly too low, which has limited improvement in the hydrophilicity of the electrode carbon felt, thereby affecting the wettability of the electrolyte to the electrode carbon felt; at the same time, the addition of carbon dots will reduce the high resistance of δ-MnO2 itself. When the amount of carbon dots added is insufficient, the high resistance of δ-MnO2 cannot be effectively suppressed, thereby reducing the electron transmission capacity of the electrode carbon felt, and the electrochemical properties of the electrode carbon felt cannot be fully exerted.

[0328] It can be seen from the test results of Example 1 and Comparative Example 9 that the electrochemical reaction resistance of the electrode carbon felt prepared in Comparative Example 9 is much higher than that of Example 1, and the energy efficiency and cycle capacity retention rate are much lower than those of Example 1. This is because, in Example 1, UIO-66 powder is added to the spinning solution. In the subsequent carbonization process, UIO-66 powder can be converted into amorphous carbon and ZrO2, thereby giving the carbon felt better conductivity and more reaction active sites; at the same time, in Example 1, the carbon felt surface is also carbon-nitrogen dual-doped and in-situ modified with δ-MnO2, which significantly increases the specific surface area of ​​the electrode carbon felt and provides more abundant reaction active sites. The electrode carbon felt after surface modification has good electrochemical properties.

[0329] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for modifying preoxidized fiber felt to improve the performance of electrode carbon felt, characterized in that: The preoxidized fiber felt modification method comprises: (I) uniformly mixing acrylonitrile, itaconic acid and dimethyl sulfoxide to obtain a precursor solution, stirring and heating the precursor solution in a nitrogen atmosphere, then adding azobisisobutyronitrile to the precursor solution and continuously stirring and heating to initiate a polymerization reaction to generate a P(AN-co-IA) copolymer, obtaining a polymer solution after the reaction is completed, and adding dimethyl sulfoxide to the polymer solution for dilution to obtain a spinning solution; (II) using zirconium ions as metal ions and 1,4-phthalic acid as organic ligands to prepare UiO-66 powder by solvothermal reaction, adding the UiO-66 powder to the spinning solution obtained in step (I), stirring and heating after mixing to obtain a spinning solution, electrospinning the spinning solution to obtain a fiber felt, and sequentially performing pre-oxidation, carbonization and surface activation treatment on the fiber felt to obtain an activated carbon felt; (III) uniformly mixing citric acid, ethylenediamine and deionized water to obtain a carbon source solution, subjecting the carbon source solution to a hydrothermal reaction, and separating and purifying the reaction product after the reaction to obtain a carbon dot powder; dispersing the carbon dot powder in a dopamine solution to obtain a modified carbon dot dispersion, immersing the activated carbon felt obtained in step (II) in the modified carbon dot dispersion, taking out the activated carbon felt after a period of time, drying it, and obtaining a modified carbon felt after high-temperature carbonization; (IV) Mix manganese sulfate, potassium permanganate and deionized water to obtain a reaction solution, transfer the reaction solution to a hydrothermal reactor, immerse the modified carbon felt obtained in step (III) in the reaction solution, and perform a hydrothermal reaction under stirring to generate δ-MnO2 in situ on the surface of the modified carbon felt. After the reaction is completed, take out the modified carbon felt, rinse it and dry it.

2. The method for modifying preoxidized fiber felt for improving the performance of electrode carbon felt according to claim 1, characterized in that: In step (I), the mass ratio of acrylonitrile, itaconic acid and dimethyl sulfoxide when mixed is (45-50):1:(210-220); The stirring rate of the precursor solution is 350-450 r / min; The stirring time of the precursor solution is 20 to 30 minutes; The heating temperature of the precursor solution is 60-70°C; The mass ratio of acrylonitrile to azobisisobutyronitrile in the precursor solution is (130-140):1; The stirring rate of the polymerization reaction is 350-450 r / min; The stirring time of the polymerization reaction is 18 to 20 hours; The heating temperature of the polymerization reaction is 60-70°C; The mass fraction of the P(AN-co-IA) copolymer in the spinning solution obtained after the dilution is 13-15wt%.

3. The method for modifying preoxidized fiber felt for improving the performance of electrode carbon felt according to claim 1, characterized in that: In step (II), the UiO-66 powder is prepared by the following method: Dissolving zirconium chloride, 1,4-phthalic acid and acetic acid in N,N-dimethylformamide, mixing well and then performing ultrasonic dispersion to obtain a precursor solution; transferring the precursor solution to a reaction kettle, stirring and heating the precursor solution to react, washing and centrifuging the reaction product in sequence after the reaction is completed, and drying the precipitate after centrifugation to obtain the UiO-66 powder; The mixing ratio of the zirconium chloride, the 1,4-phthalic acid, the acetic acid and the N,N-dimethylformamide is 1 mmol:1 mmol:(3-5) mL:(25-35) mL; The ultrasonic power used in the ultrasonic dispersion is 200-300W; The ultrasonic dispersion time is 10 to 20 minutes; The stirring rate of the precursor solution is 200-300 r / min; The heating temperature of the precursor solution is 120-130°C; The reaction time of the precursor solution is 20 to 25 hours; The centrifugal speed of the reaction product after washing is 8000-9000 r / min; The centrifugation time after washing the reaction product is 3 to 5 minutes; The drying temperature of the precipitate is 80-100°C; The drying time of the precipitate is 12 to 24 hours.

4. The method for modifying preoxidized fiber felt for improving the performance of electrode carbon felt according to claim 1, characterized in that: In step (II), the mass fraction of UiO-66 powder in the spinning solution is 0.5-1.5wt%; The heating temperature when the spinning solution and the UiO-66 powder are mixed is 70-80°C; The stirring rate when the spinning solution and the UiO-66 powder are mixed is 300-400 r / min; The stirring time when the spinning solution and the UiO-66 powder are mixed is 10 to 15 hours; The diameter of the needle used in the electrospinning is 0.5 to 1.5 mm; The relative humidity of the electrospinning environment is 35-45%; The ambient temperature of the electrospinning is 30-40°C; The voltage of the electrospinning is 20 to 30 kV; The electrospinning propulsion speed is 1.5 to 2.5 mL / h; The distance between the tip of the electrospinning needle and the receiving screen is 10 to 20 cm; The fiber felt has a thickness of 1 to 3 mm.

5. The method for modifying preoxidized fiber felt for improving the performance of electrode carbon felt according to claim 1, characterized in that: In step (II), the pre-oxidation process is carried out in an oxidation furnace, and the pre-oxidation process adopts a six-stage gradient pre-oxidation process, which specifically includes the following steps: In an air atmosphere, the fiber felt is heated to a first pre-oxidation temperature at a first heating rate and kept warm to complete a first pre-oxidation process; then, it is continuously heated to a second pre-oxidation temperature at a second heating rate and kept warm to complete a second pre-oxidation process; then, it is continuously heated to a third pre-oxidation temperature at a third heating rate and kept warm to complete a third pre-oxidation process; then, it is continuously heated to a fourth pre-oxidation temperature at a fourth heating rate and kept warm to complete a fourth pre-oxidation process; then, it is continuously heated to a fifth pre-oxidation temperature at a fifth heating rate and kept warm to complete a fifth pre-oxidation process; then, it is continuously heated to a sixth pre-oxidation temperature at a sixth heating rate and kept warm to complete a sixth pre-oxidation process; after the insulation is completed, it is cooled to room temperature to obtain a pre-oxidation felt; The first heating rate is 5 to 10°C / min; The first pre-oxidation temperature is 220-225°C; Keeping the temperature at the first pre-oxidation temperature for 8 to 10 minutes; In the first pre-oxidation process, the oxidation furnace is pressurized to 0.12-0.13 MPa while heating and raising the temperature, and the pressure is maintained while the temperature is maintained; The second heating rate is 2-5°C / min; The second pre-oxidation temperature is 230-235°C; Keeping the temperature at the second pre-oxidation temperature for 8 to 10 minutes; In the second pre-oxidation process, the oxidation furnace is pressurized to 0.14-0.15 MPa while heating and raising the temperature, and the pressure is maintained while the temperature is maintained; The third heating rate is 2-5°C / min; The third pre-oxidation temperature is 240-245°C; Keeping the temperature at the third pre-oxidation temperature for 8 to 10 minutes; In the third pre-oxidation process, the pressure in the oxidation furnace is reduced to 0.12-0.13 MPa while heating and raising the temperature, and the pressure is maintained while keeping the temperature; The fourth heating rate is 2-5°C / min; The fourth pre-oxidation temperature is 245-250° C. Keeping the temperature at the fourth pre-oxidation temperature for 8 to 10 minutes; In the fourth pre-oxidation process, the pressure in the oxidation furnace is continuously reduced to 0.1-0.11 MPa while heating and raising the temperature, and the pressure is maintained while keeping the temperature; The fifth heating rate is 2-5°C / min; The fifth pre-oxidation temperature is 250-255°C; Keeping the temperature at the fifth pre-oxidation temperature for 8 to 10 minutes; In the fifth pre-oxidation process, the oxidation furnace is pressurized to 0.12-0.13 MPa while heating and raising the temperature, and the pressure is maintained while the temperature is maintained; The sixth heating rate is 2-5°C / min; The sixth pre-oxidation temperature is 255-260° C. Keeping the temperature at the sixth pre-oxidation temperature for 8 to 10 minutes; In the sixth pre-oxidation process, the oxidation furnace is pressurized to 0.13-0.14 MPa while heating and raising the temperature, and the pressure is maintained while maintaining the temperature.

6. The method for modifying preoxidized fiber felt for improving the performance of electrode carbon felt according to claim 5, characterized in that: In step (II), the carbonization process specifically comprises the following steps: In a nitrogen atmosphere, heating the pre-oxidized felt obtained after pre-oxidation to a first carbonization temperature at a seventh heating rate and keeping the temperature, so as to complete a low-temperature carbonization process; Subsequently, the heating is continued at the eighth heating rate to the second carbonization temperature and the temperature is kept to complete the high-temperature carbonization process; after the temperature is kept, the carbon felt is cooled to room temperature to obtain the carbon felt; The seventh heating rate is 5-8°C / min; The first carbonization temperature is 600-700°C; Keeping the temperature at the first carbonization temperature for 3 to 6 minutes; The eighth heating rate is 5-8°C / min; The second carbonization temperature is 1500-1600°C; The second carbonization temperature is maintained for 2 to 4 minutes.

7. The method for modifying preoxidized fiber felt for improving the performance of electrode carbon felt according to claim 6, characterized in that: In step (II), the surface activation treatment process includes: The sucrose solution is uniformly sprayed on the surface of the carbon felt, and after drying, the carbon felt sprayed with the sucrose solution is placed in an activation furnace, and an activation gas is introduced into the activation furnace to heat and activate the carbon felt, and after the heating and activation is completed, the carbon felt is cooled to room temperature to complete the surface activation treatment, thereby obtaining the activated carbon felt; The mass fraction of the sucrose solution is 1-2wt%; The spraying amount of the sucrose solution on the carbon felt surface is 4-5 mL / m 2 ; The activation gas is composed of argon, air and carbon dioxide, wherein the volume flow ratio of the argon, air and carbon dioxide is 1:(0.5-0.6):(0.2-0.3); The flow rate of the activated gas is 80-120 m 3 / h; The heating rate of the heating activation is 10-12°C / min; The heating temperature of the heating activation is 900-1000°C; The heat preservation time of the heating activation is 15 to 25 minutes.

8. The method for modifying preoxidized fiber felt for improving the performance of electrode carbon felt according to claim 1, characterized in that: In step (III), the molar ratio of citric acid to ethylenediamine is 1:(18-20); The mixing ratio of the citric acid and deionized water is 1 g: (100-120) mL; Before the carbon source solution is subjected to a hydrothermal reaction, an alkali solution having a mass fraction of 20 to 30 wt % is added dropwise to the carbon source solution to adjust the pH value thereof to 8 to 9; The temperature of the hydrothermal reaction of the carbon source solution is 170-180°C; The hydrothermal reaction time of the carbon source solution is 10 to 15 hours; The separation and purification process comprises: centrifugally filtering the reaction product, dialyzing the supernatant after centrifugation, and freeze-drying the dialyzed retentate; During the separation and purification process, the centrifugal speed of the centrifugal filtration is 8000-9000 r / min; In the separation and purification process, the centrifugation time of the centrifugal filtration is 10 to 20 minutes; In the separation and purification process, the molecular weight cutoff of the dialysis bag used in the dialysis is 800-1000Da; During the separation and purification process, the freeze-drying temperature is -50 to -60°C; During the separation and purification process, the freeze-drying time is 20 to 25 hours; The dopamine solution consists of dopamine hydrochloride and Tris-HCl buffer; The concentration of dopamine hydrochloride in the dopamine solution is 0.5 to 1.5 g / L; The mass ratio of the carbon dot powder to the dopamine hydrochloride in the dopamine solution is 1:(1.3-1.5); The ratio of the activated carbon felt to the modified carbon dot dispersion is 1 g: (100-120) mL; The activated carbon felt is immersed in the modified carbon point dispersion for 5 to 10 hours; The drying temperature of the activated carbon felt is 70-80°C; The activated carbon felt is dried for 3 to 5 hours; The temperature of high temperature carbonization of the activated carbon felt is 850-950°C; The high temperature carbonization time of the activated carbon felt is 0.5 to 1.5 hours.

9. The method for modifying preoxidized fiber felt for improving the performance of electrode carbon felt according to claim 1, characterized in that: In step (IV), the concentration of manganese sulfate in the reaction solution is 15 to 25 g / L; The concentration of potassium permanganate in the reaction solution is 110-120 g / L; The ratio of the modified carbon felt to the reaction solution is 1 g: (100-120) mL; The temperature of the hydrothermal reaction is 130-150°C; The hydrothermal reaction time is 15 to 20 hours; The stirring rate of the hydrothermal reaction is 400-500 r / min; The drying temperature is 70-80°C; The drying time is 12 to 24 hours.

10. An electrode carbon felt prepared by the preoxidized fiber felt modification method for improving the performance of electrode carbon felt according to any one of claims 1 to 9.

Citation Information

Cited By

  • Modified flow battery electrode capable of simultaneously improving activity and stability and preparation method of modified flow battery electrode

    CN119674107A